Biological material adhesion inhibitor

A copolymer with anionic and cationic groups forms a coating film that suppresses biological substance adhesion on substrates, addressing the adhesion issues in medical devices and promoting cell culture by reducing protein and cell attachment.

JP7616203B2Active Publication Date: 2025-01-17NISSAN CHEM CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022501996
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-19
Filing Date
2021-02-18
Publication Date
2025-01-17
Estimated Expiration
2041-02-18

AI Technical Summary

Technical Problem

Existing coating materials fail to effectively suppress the adhesion of biological substances such as proteins and cells on medical devices and substrates, leading to issues in cell culture and medical applications.

Method used

A copolymer containing specific anionic and cationic groups with a crosslinked structure is used to form a coating film, which is applied to substrates to suppress the adhesion of biological substances by forming ionic bonds, thereby enhancing the film's ability to resist water and inhibit adhesion.

Benefits of technology

The coating film effectively reduces the adhesion of biological substances by up to 50% or less, promoting cell culture and maintaining substrate integrity by preventing protein and cell attachment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007616203000022
    Figure 0007616203000022
  • Figure 0007616203000023
    Figure 0007616203000023
  • Figure 0007616203000024
    Figure 0007616203000024
Patent Text Reader

Abstract

The purpose of the present invention is to provide a composition for forming a coating film, said composition being highly compatible with biomaterials, a coating film, a substrate provided with the coating film and a method for producing the same. A composition for forming a coating film that comprises a copolymer, said copolymer being obtained by polymerizing a monomer mixture which contains compounds represented by formulae (1), (2) and (3) (wherein R1 to R6, n and m are each as defined in the description and claims) and in which the compound represented by formula (3) is contained at a specific ratio, and a solvent and that is capable of inhibiting the adhesion of biomaterials; a coating film obtained from the composition; a substrate provided with the coating film; and a method for producing the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition for forming a coating film having a biological material adhesion inhibiting ability, a coating film obtained from said composition, a substrate provided with said coating film, and a method for producing the same. [Background technology]

[0002] Coating materials capable of inhibiting adhesion of various biological substances to medical instruments and equipment such as artificial dialysis machines, artificial organs, and medical devices, as well as coating materials for promoting cell culture have been proposed.

[0003] The present inventors have previously reported that a coating agent containing a copolymer having specific anionic groups and cationic groups can be firmly attached to any type of substrate, and that after adhesion, it forms a coating film with excellent resistance to aqueous solvents and exhibits excellent adhesion inhibitory properties for biological materials (e.g., platelets, fibrinogen, etc.) (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2014 / 196650 [Patent Document 2] International Publication No. 2016 / 093293 Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention provides a composition for forming a coating film having a biological material adhesion inhibiting ability, a coating film obtained from the composition, a substrate provided with the coating film, and a method for producing the same. [Means for solving the problem]

[0006] The present inventors discovered that a copolymer containing specific anionic groups and cationic groups exhibits excellent ability to inhibit the adhesion of biological materials by containing crosslinked structures in a predetermined ratio, and thus completed the present invention. That is, the present invention is as follows.

[0007] [1] The following formula (1): [ka] (In the formula, R 1 represents a hydrogen atom or a linear or branched alkyl group having 1 to 6 carbon atoms; R 2 represents a linear or branched alkylene group having 1 to 6 carbon atoms, and n represents an integer of 1 to 30. A compound represented by the following formula (2): [ka] (In the formula, R 3 represents a hydrogen atom or a linear or branched alkyl group having 1 to 5 carbon atoms; R 4 represents a monovalent organic group having cationic properties. and a compound represented by the following formula (3): [ka] (In the formula, R 5 each independently represents a hydrogen atom or a linear or branched alkyl group having 1 to 6 carbon atoms; R 6 represents a linear or branched alkylene group having 1 to 10 carbon atoms which may be substituted with a halogen atom, and m represents an integer of 1 to 30. The present invention relates to a composition for forming a coating film having an ability to inhibit adhesion of biological materials, the composition comprising: a monomer mixture containing a compound represented by formula (3), wherein the ratio of the compound represented by formula (3) to the total mass of the monomer mixture is 2 to 40 mass %, and a solvent.

[0008] [2] A coating film having an ability to inhibit adhesion of biological materials, characterized in that it is a coating film made of the coating film-forming composition described in [1] above.

[0009] [3] A substrate having the coating film described in [2] above on its surface, the substrate having the ability to inhibit adhesion of biological materials.

[0010] [4] A substrate having the ability to inhibit adhesion of biological materials described in [3] above, which is used for cell culture.

[0011] [5] A method for producing a substrate having adhesion-inhibiting properties against biological material, comprising a step of applying the coating film-forming composition according to [1] above to a substrate, and then a step of drying the applied coating film.

[0012] [6] The following formula (1): [ka] (In the formula, R 1 represents a hydrogen atom or a linear or branched alkyl group having 1 to 6 carbon atoms; R 2 represents a linear or branched alkylene group having 1 to 6 carbon atoms, and n represents an integer of 1 to 30. A compound represented by the following formula (2): [ka] (In the formula, R 3 represents a hydrogen atom or a linear or branched alkyl group having 1 to 6 carbon atoms; R 4 represents a monovalent organic group having cationic properties. and a compound represented by the following formula (3): [ka] (In the formula, R 5each independently represents a hydrogen atom or a linear or branched alkyl group having 1 to 6 carbon atoms; R 6 represents a linear or branched alkylene group having 1 to 10 carbon atoms which may be substituted with a halogen atom, and m represents an integer of 1 to 30. a monomer mixture containing a compound represented by formula (3) in an amount of 2 to 40 mass% relative to the total mass of the monomer mixture, Effect of the Invention

[0013] The coating film-forming composition of the present invention has an excellent ability to inhibit adhesion of biological materials by containing a copolymer obtained by polymerizing a monomer mixture containing a compound represented by formula (3) in a predetermined ratio together with the compounds represented by formula (1) and formula (2). In particular, the composition of the present invention has an improved ability to inhibit adhesion of biological materials compared to conventional compositions containing a copolymer containing a specific anionic group and a cationic group by containing a copolymer containing a specific anionic group and a cationic group. Specifically, a substrate provided with a coating film formed from the coating film-forming composition of the present invention has excellent adhesion inhibition ability for biological materials such as proteins and excellent cell culture promotion ability. [Brief description of the drawings]

[0014] [Figure 1] 1 is a micrograph of a well coated with the coating film-forming composition prepared in Preparation Example 3, which is attached to Test Example 1. [Diagram 2] 1 is a micrograph of a well coated with the coating film-forming composition prepared in Preparation Example 4, which is attached to Test Example 1. [Diagram 3] 1 is a micrograph of a well coated with the coating film-forming composition prepared in Preparation Example 5, attached to Test Example 1. [Figure 4]1 is a micrograph of a well coated with the coating film-forming composition prepared in Comparative Preparation Example 4, which is attached to Test Example 1. [Diagram 5] 1 is a micrograph of a well (positive control) coated with the composition for forming a coating film prepared in Reference Example 1, which is used in Test Example 1. [Figure 6] 1 is a micrograph of an uncoated well (negative control) used in Test Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] <Terminology explanation> The terms used in the present invention have the following definitions unless otherwise specified.

[0016] In the present invention, a "halogen atom" means a fluorine atom, a chlorine atom, a bromine atom or an iodine atom.

[0017] In the present invention, an "ester bond" means -C(=O)-O- or -OC(=O)-, an "amide bond" means -NHC(=O)- or -C(=O)NH-, an "ether bond" means -O-, and a "phosphodiester bond" means -OP(=O)(OH)-O-.

[0018] In the present invention, the term "alkylene group" refers to a divalent group of a saturated aliphatic hydrocarbon. The term "alkylene group having 1 to 6 carbon atoms" means a linear, branched or cyclic alkylene group having 1 to 6 carbon atoms, and examples thereof include linear alkylene groups such as a methylene group, an ethylene group, a trimethylene group, a tetramethylene group, a pentamethylene group or a hexamethylene group; a propylene group, a 1-methyltrimethylene group, a 2-methyltrimethylene group, a 1,1-dimethylethylene group, a 1,2-dimethylethylene group, an ethylethylene group, a 1-methyltetramethylene group, a 2-methyltetramethylene group, a 1,1-dimethyltrimethylene group, a 1,2-dimethyltrimethylene group, a 1,3-dimethyltrimethylene group, a 2,2-dimethyltrimethylene group, a 1-ethyltrimethylene group, a 2-ethylethylene group, a branched alkylene groups such as ethyltrimethylene group, propylethylene group, (1-methylethyl)ethylene group, 1-methylpentamethylene group, 2-methylpentamethylene group, 3-methylpentamethylene group, 1,1-dimethyltetramethylene group, 1,2-dimethyltetramethylene group, 1,3-dimethyltetramethylene group, 1,4-dimethyltetramethylene group, 2,2-dimethyltetramethylene group, 2,3-dimethyltetramethylene group, 1-ethyltetramethylene group, 2-ethyltetramethylene group, 1,1,2-trimethyltrimethylene group, 1,2,2-trimethyltrimethylene group, 1-ethyl-1-methyltrimethylene group, and 1-ethyl-2-methyltrimethylene group;or 1,2-cyclopropanediyl group, 1,2-cyclobutanediyl group, 1,3-cyclobutanediyl group, 1-methyl-1,2-cyclopropanediyl group, 3-methyl-1,2-cyclopropanediyl group, 1,2-cyclopentanediyl group, 1,3-cyclopentanediyl group, 1-methyl-1,2-cyclobutanediyl group, 3-methyl-1,2-cyclobutanediyl group, 1-methyl-1,3-cyclobutanediyl group, 2-methyl-1,3-cyclobutanediyl group, 1,2-dimethyl-1,2-cyclopropanediyl group, 1,3-dimethyl-1,2-cyclopropanediyl group, 3,3-dimethyl-1,2-cyclopropanediyl Examples of cyclic alkylene groups include 1-ethyl-1,2-cyclopropanediyl group, 1,2-cyclohexanediyl group, 1,3-cyclohexanediyl group, 1,4-cyclohexanediyl group, 1-methyl-1,2-cyclopentanediyl group, 1-methyl-1,3-cyclopentanediyl group, 3-methyl-1,2-cyclopentanediyl group, 4-methyl-1,2-cyclopentanediyl group, 2-methyl-1,3-cyclopentanediyl group, 1-ethyl-1,2-cyclobutanediyl group, 1-ethyl-1,3-cyclobutanediyl group, 2-ethyl-1,3-cyclobutanediyl group, and 4-methyl-1,2-cyclopentanediyl group. The "alkylene group having 1 to 6 carbon atoms" is preferably a linear or branched alkylene group having 1 to 6 carbon atoms, more preferably a linear or branched alkylene group having 2 to 5 carbon atoms, and particularly preferably an ethylene group or a propylene group.

[0019] In the present invention, the term "linear or branched alkylene group having 1 to 10 carbon atoms which may be substituted with a halogen atom" means "linear or branched alkylene group having 1 to 10 carbon atoms" or "linear or branched alkylene group having 1 to 10 carbon atoms and substituted with one or more halogen atoms". Examples of the "straight-chain or branched alkylene group having 1 to 10 carbon atoms" include the above-mentioned examples of the "straight-chain or branched alkylene group having 1 to 6 carbon atoms", as well as a heptamethylene group, an octamethylene group, a nonamethylene group, a decamethylene group, or an isomer thereof. The "straight-chain or branched alkylene group having 1 to 10 carbon atoms" is preferably a straight-chain or branched alkylene group having 1 to 6 carbon atoms, more preferably a straight-chain or branched alkylene group having 2 to 5 carbon atoms, and particularly preferably an ethylene group or a propylene group. The term "linear or branched alkylene group having 1 to 10 carbon atoms substituted with one or more halogen atoms" means the above-mentioned "linear or branched alkylene group having 1 to 10 carbon atoms" in which at least one hydrogen atom has been replaced with a halogen atom, preferably a linear or branched alkylene group having 1 to 6 carbon atoms in which some or all of the hydrogen atoms have been replaced with a halogen atom, more preferably a linear or branched alkylene group having 2 to 5 carbon atoms in which some or all of the hydrogen atoms have been replaced with a halogen atom, and particularly preferably an ethylene group or propylene group in which one or all of the hydrogen atoms have been replaced with a halogen atom.

[0020] In the present invention, "a linear or branched alkylene group having 1 to 6 carbon atoms which may be interrupted by an ester bond, an amide bond, an ether bond, or a phosphodiester bond" means "a linear or branched alkylene group having 1 to 6 carbon atoms" or "a linear or branched alkylene group having 1 to 6 carbon atoms which is interrupted by an ester bond, an amide bond, an ether bond, or a phosphodiester bond". Examples of the "straight-chain or branched alkylene group having 1 to 6 carbon atoms" are as described above. The "straight-chain or branched alkylene group having 1 to 6 carbon atoms, which may be interrupted by an ester bond, an amide bond, an ether bond or a phosphodiester bond" is a straight-chain or branched alkylene group having 1 to 6 carbon atoms, which may be interrupted by at least one methylene (-CH 2-) group is replaced by the above-mentioned ester bond, amide bond, ether bond or phosphodiester bond.

[0021] The term "alkyl group" refers to a monovalent group of a linear, branched, or cyclic saturated aliphatic hydrocarbon. Examples of the linear or branched alkyl group having 1 to 6 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, an s-butyl group, a t-butyl group, an n-pentyl group, a 1-methylbutyl group, a 2-methylbutyl group, a 3-methylbutyl group, a 1,1-dimethylpropyl group, a 1,2-dimethylpropyl group, a 2,2-dimethylpropyl group, a 1-ethylpropyl group, an n-hexyl group, a 1-methylpentyl group, a 2-methylpentyl group, a 3-methylpentyl group, a 1,1-dimethylbutyl group, a 1,2-dimethylbutyl group, a 2,2-dimethylbutyl group, and a 1-ethylbutyl group.

[0022] In the present invention, the term "aryl group" refers to a monovalent monocyclic or polycyclic aromatic hydrocarbon group. The "aryl group" is preferably an aryl group having 6 to 10 carbon atoms, and more preferably a phenyl group, a naphthyl group, an anthryl group, or the like.

[0023] In the present invention, the "aralkyl group having 7 to 16 carbon atoms" means the above-mentioned "linear or branched alkyl group having 1 to 6 carbon atoms" in which at least one hydrogen atom is replaced with the above-mentioned "aryl group having 6 to 10 carbon atoms", and examples thereof include a benzyl group, a phenethyl group, an α-methylbenzyl group, etc.

[0024] In the present invention, the (meth)acrylate compound means both an acrylate compound and a methacrylate compound. For example, (meth)acrylic acid means acrylic acid and methacrylic acid.

[0025] In the present invention, "cation" or "cationic group" means a positive ion or a cationic group, and includes those that can dissociate in water to become a cation or a cationic group. Thus, "monovalent organic groups having cationic properties" include monovalent organic groups that can dissociate in water to become a cationic group. Typical examples of "monovalent organic groups having cationic properties" are monovalent groups having a primary amine, secondary amine, tertiary amine, or quaternary ammonium structure.

[0026] In the present invention, examples of biological materials include proteins, sugars, nucleic acids, and cells, or combinations thereof. For example, proteins include fibrinogen, bovine serum albumin (BSA), human albumin, various globulins, β-lipoprotein, various antibodies (IgG, IgA, IgM), peroxidase, various complements, various lectins, fibronectin, lysozyme, von Willebrand factor (vWF), serum γ-globulin, pepsin, ovalbumin, insulin, histone, ribonuclease, collagen, cytochrome c, and sugars include, for example, glycerol, ribonuclease, collagen, cytochrome c, and ... Glucose, galactose, mannose, fructose, heparin, hyaluronic acid, for example, nucleic acids such as deoxyribonucleic acid (DNA) and ribonucleic acid (RNA), for example, cells such as fibroblasts, bone marrow cells, B lymphocytes, T lymphocytes, neutrophils, erythrocytes, platelets, macrophages, monocytes, osteocytes, pericytes, dendritic cells, keratinocytes, adipocytes, mesenchymal cells, epithelial cells, epidermal cells, endothelial cells, vascular endothelial cells, hepatic parenchymal cells, chondrocytes, and cumulus cells , nervous system cells, glial cells, neurons, oligodendrocytes, microglia, astrocytes, cardiac cells, esophageal cells, muscle cells (e.g., smooth muscle cells or skeletal muscle cells), pancreatic beta cells, melanocytes, hematopoietic progenitor cells, mononuclear cells, embryonic stem cells (ES cells), embryonic tumor cells, embryonic germ stem cells, induced pluripotent stem cells (iPS cells), neural stem cells, hematopoietic stem cells, mesenchymal stem cells, hepatic stem cells, pancreatic stem cells, muscle stem cells, germ stem cells, intestinal stem cells, cancer stem cells Examples of the cells that can be used for adhesion include hair follicle, hair follicle stem cells, and various cell lines (e.g., HCT116, Huh7, HEK293 (human fetal kidney cells), HeLa (human cervical cancer cell line), HepG2 (human hepatoma cell line), UT7 / TPO (human leukemia cell line), CHO (Chinese hamster ovary cell line), MDCK, MDBK, BHK, C-33A, HT-29, AE-1, 3D9, Ns0 / 1, Jurkat, NIH3T3, PC12, S2, Sf9, Sf21, High Five, Vero), and the coating film of the present invention has a particularly high adhesion-inhibiting ability against platelets. The coating film of the present invention has a particularly high adhesion-inhibiting ability against serum containing a mixture of proteins and sugars. The coating film of the present invention has a particularly high adhesion-inhibiting ability against cells, particularly embryonic fibroblasts.The coating film of the present invention has a particularly high adhesion-inhibiting ability, particularly for mouse embryonic fibroblast cells (eg, C3H10T1 / 2).

[0027] The ability to inhibit adhesion of biological materials means, for example, When the biological material is a protein, the relative mass per unit area (%) ((mass per unit area (ng / cm) in the example) compared to when there is no coating film is measured by QCM-D measurement performed by the method described in the example. 2 ) / (Mass per unit area of ​​comparative example (ng / cm 2 ))) is 50% or less, preferably 30% or less, and more preferably 20% or less; When the biological material is cells, this means that when cell attachment is observed using a fluorescence microscope using the method described in the Examples, no cell attachment or spreading is observed, and the formation of cell aggregates is observed, compared to the control.

[0028] Description of the invention (Composition for forming coating film) The composition for forming a coating film of the present invention has the following formula (1): [ka] (In the formula, R 1 represents a hydrogen atom or a methyl group, and R 2 represents an alkylene group having 1 to 6 carbon atoms, and n represents an integer of 1 to 30. A compound represented by the following formula (2): [ka] (In the formula, R 3 represents a hydrogen atom or a methyl group, and R 4 represents a monovalent organic group having cationic properties. and a compound represented by the following formula (3): [ka] (In the formula, R 5 each independently represents a hydrogen atom or a linear or branched alkyl group having 1 to 6 carbon atoms; R 6 represents a linear or branched alkylene group having 1 to 10 carbon atoms which may be substituted with a halogen atom, and m represents an integer of 1 to 30. The present invention includes a monomer mixture containing a compound represented by formula (3), wherein the ratio of the compound represented by formula (3) to the total mass of the monomer mixture is 2 to 40 mass %, and a solvent.

[0029] In the compound of formula (1) which is a monomer component of the copolymer according to the present invention, R 1 represents a hydrogen atom or a methyl group, and R 2 represents an alkylene group having 1 to 6 carbon atoms, preferably a linear or branched alkylene group having 1 to 6 carbon atoms, more preferably a linear or branched alkylene group having 2 to 5 carbon atoms, particularly preferably an ethylene group or a propylene group; n represents an integer of 1 to 30, preferably an integer of 1 to 20, more preferably an integer of 2 to 10, and particularly preferably an integer of 3 to 6.

[0030] Specific examples of the compound of the above formula (1) include acid phosphooxyethyl (meth)acrylate, 3-chloro-2-acid phosphooxypropyl (meth)acrylate, acid phosphooxypropyl (meth)acrylate, acid phosphooxymethyl (meth)acrylate, acid phosphooxypolyoxyethylene glycol mono(meth)acrylate, and acid phosphooxypolyoxypropylene glycol mono(meth)acrylate, and among these, acid phosphooxyethyl methacrylate (=2-(methacryloyloxy)ethyl phosphate), acid phosphooxypolyoxyethylene glycol monomethacrylate, and acid phosphooxypolyoxypropylene glycol monomethacrylate are preferably used.

[0031] The structural formulas of acid phosphooxyethyl methacrylate (=2-(methacryloyloxy)ethyl phosphate), acid phosphooxy polyoxyethylene glycol monomethacrylate, and acid phosphooxy polyoxypropylene glycol monomethacrylate are represented by the following formulas (1-1) to (1-3), respectively.

[0032] [ka]

[0033] In the compound of formula (2) which is a monomer component of the copolymer according to the present invention, R 3 represents a hydrogen atom or a methyl group, and R 4 represents a monovalent organic group having cationic properties, and is typically a monovalent group having a primary amine, secondary amine, tertiary amine or quaternary ammonium structure. Examples of the monovalent group having a primary amine, secondary amine, tertiary amine or quaternary ammonium structure include those represented by the formula: -R 4a -NH 2 , -R 4a -NHR, -R 4a -NRR′, -R 4a -N + RR′R″ [where R 4a represents an alkylene group having 1 to 6 carbon atoms which may be interrupted by an ester bond, an amide bond, an ether bond or a phosphodiester bond, and R, R' and R" are each independently a straight-chain or branched alkyl group having 1 to 6 carbon atoms, an aryl group having 6 to 10 carbon atoms, or an aralkyl group having 7 to 16 carbon atoms. In the present invention, a monovalent group having a primary amine, secondary amine or tertiary amine structure may be quaternized or salified, and similarly, a monovalent group having a quaternary ammonium structure may be salified.

[0034] Specific examples of the compound of the above formula (2) include dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylate, 2-(t-butylamino)ethyl (meth)acrylate, (meth)acryloylcholine chloride, and 2-(meth)acryloyloxyethyl phosphorylcholine (MPC).

[0035] The structural formulas of 2-(dimethylamino)ethyl methacrylate, methacryloylcholine chloride, and 2-methacryloyloxyethyl phosphorylcholine (MPC) are represented by the following formulas (2-1) to (2-3), respectively.

[0036] [ka]

[0037] The compound of formula (3), which is a monomer component of the copolymer according to the present invention, is a bifunctional monomer having crosslinking properties. 5 each independently represents a hydrogen atom or a linear or branched alkyl group having 1 to 6 carbon atoms, preferably a hydrogen atom or a methyl group; R 6 represents a linear or branched alkylene group having 1 to 10 carbon atoms which may be substituted with a halogen atom, preferably a linear or branched alkylene group having 1 to 6 carbon atoms which may be substituted with a halogen atom, more preferably a linear or branched alkylene group having 1 to 6 carbon atoms which may be substituted with a chlorine atom, particularly preferably an ethylene group, propylene group or trimethylene group, and m represents an integer of 1 to 30, preferably an integer of 1 to 20, more preferably an integer of 1 to 10, even more preferably an integer of 1 to 6, and particularly preferably an integer of 1 to 4.

[0038] Specific examples of the compound of the above formula (3) include poly(ethylene glycol) di(meth)acrylate, poly(trimethylene glycol) di(meth)acrylate, poly(propylene glycol) di(meth)acrylate, and the like.

[0039] The structural formulas of poly(ethylene glycol) dimethacrylate, poly(trimethylene glycol) dimethacrylate, and poly(propylene glycol) dimethacrylate are represented by the following formulas (3-1) to (3-3), respectively.

[0040] [ka]

[0041] The copolymer according to the present invention is obtained by polymerizing a monomer mixture containing the compounds of the above formulae (1), (2) and (3) as monomer components. Such a monomer mixture may contain an ethylenically unsaturated monomer, or a polysaccharide or a derivative thereof as an optional fourth component, as long as the effect of the present invention (i.e., the ability to inhibit adhesion of biological materials, etc.) is not impaired. Examples of the ethylenically unsaturated monomer include one or more ethylenically unsaturated monomers selected from the group consisting of (meth)acrylic acid and its esters, vinyl acetate, vinylpyrrolidone, ethylene, vinyl alcohol, and hydrophilic functional derivatives thereof. Examples of polysaccharides or derivatives thereof include cellulose-based polymers such as hydroxyalkyl cellulose (e.g., hydroxyethyl cellulose or hydroxypropyl cellulose), starch, dextran, and curdlan. The copolymer according to the present invention is preferably obtained by polymerizing a monomer mixture containing only the compounds of the above formulae (1), (2) and (3) as monomer components.

[0042] The copolymer according to the present invention is obtained by polymerizing a monomer mixture containing the compounds of the above formulas (1), (2) and (3) as monomer components, and characterized in that the ratio of the compound of the formula (3) to the total mass of the monomer components contained in the monomer mixture is 2 to 40 mass%. By containing the compound of the formula (3) as a bifunctional monomer in the range of 2 to 40 mass%, preferably in the range of 3 to 35 mass%, more preferably in the range of 5 to 30 mass%, relative to the total mass of the monomer components contained in the monomer mixture, the coating film forming composition of the present invention, which contains the copolymer obtained from the monomer mixture, can obtain excellent adhesion suppression ability of biological materials. The monomer mixture may contain two or more compounds of formula (3).

[0043] In the monomer mixture, the ratio of the compound of formula (1) to the total mass of the monomer components is 10 to 95 mass%, preferably 10 to 80 mass%, and more preferably 45 to 75 mass%. The monomer mixture may contain two or more types of compounds of formula (1).

[0044] In the monomer mixture, the ratio of the compound of formula (2) to the total mass of the monomer components is 3 to 90 mass%, preferably 10 to 70 mass%, and more preferably 15 to 35 mass%. The monomer mixture may contain two or more types of compounds of formula (2).

[0045] The copolymer according to the present invention can be synthesized by a method such as radical polymerization, anionic polymerization, or cationic polymerization, which is a general method for synthesizing (meth)acrylic polymers. The form of the copolymer can be various methods such as solution polymerization, suspension polymerization, emulsion polymerization, and bulk polymerization. In one embodiment, the copolymer can be prepared by a production method including a step of reacting (polymerizing) a monomer mixture containing the compounds of the above formulas (1), (2), and (3) in a solvent at a total concentration of the monomer components of 0.01 to 20% by mass.

[0046] The solvent in the polymerization reaction may be water, a phosphate buffer solution, an alcohol such as ethanol, or a mixed solvent of these, but preferably contains water or ethanol. It is more preferable that the solvent contains 10% by mass or more and 100% by mass or less of water or ethanol. It is more preferable that the solvent contains 50% by mass or more and 100% by mass or less of water or ethanol. It is more preferable that the solvent contains 80% by mass or more and 100% by mass or less of water or ethanol. It is more preferable that the solvent contains 90% by mass or more and 100% by mass or less of water or ethanol. The total of water and ethanol is preferably 100% by mass.

[0047] In order to efficiently advance the polymerization reaction, it is desirable to use a polymerization initiator. Examples of the polymerization initiator include a "thermal radical polymerization initiator" or a "photoradical polymerization initiator." Examples of the "thermal radical polymerization initiator" include 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile) (FUJIFILM Wako Pure Chemical Industries, Ltd. product name: V-65, 10-hour half-life temperature: 51°C), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 1-[(1-cyano 2,2′-Azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride (FUJIFILM Wako Pure Chemical Industries, Ltd.; VA-044, 10-hour half-life temperature; 44°C), 2,2′-Azobis[2-(2-imidazolin-2-yl)propane] (FUJIFILM Wako Pure Chemical Industries, Ltd.; VA-061, 10-hour half-life temperature; 61°C), 2,2′-Azobis(2-methylpropionamidine)dihydrochloride, 2,2′-Azo(2-methyl-N-(2-hydroxyethyl) Propionamide (FUJIFILM Wako Pure Chemical Industries, Ltd. product name: VA-086, 10-hour half-life temperature: 86°C), benzoyl peroxide (BPO), 2,2′-azobis(N-(2-carboxyethyl)-2-methylpropionamidine) n-hydrate (FUJIFILM Wako Pure Chemical Industries, Ltd. product name: VA-057, 10-hour half-life temperature: 57°C), 4,4′-azobis(4-cyanopentanoic acid) (FUJIFILM Wako Pure Chemical Industries, Ltd. product name: VA-501), 2,2′-azobis[2-(2-imidazoline 1,1'-azobis(1-cyclohexanecarboxylate) (Fujifilm Wako Pure Chemical Industries, Ltd. product name: VE-073), and the like.

[0048] Examples of the "photoradical polymerization initiator" include acetophenone, chloroacetophenone, hydroxyacetophenone, 2-aminoacetophenone, dialkylaminoacetophenone, 2,2-diethoxyacetophenone, 2,2-dimethoxy-2'-phenylacetophenone (BASF product name: Irgacure 651), 2-hydroxy-2-methyl-1-phenylpropanone (BASF product name: Irgacure 1173), 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxymethylpropanone (BASF product name: Irgacure 1173), and the like. Acetophenones such as 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl}-2-methyl-1-propan-1-one (BASF product name: Irgacure 127), 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one (BASF product name: Irgacure 907), and 2-benzyl-2-(dimethylamino)-4-morpholinobutyrophenone (BASF product name: Irgacure 369) Benzoins such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and 1-hydroxycyclohexyl phenyl ketone (BASF product name: Irgacure 184); benzophenone, benzoylbenzoic acid, methyl benzoylbenzoate, methyl-o-benzoylbenzoate, 4-phenylbenzophenone, hydroxybenzophenone, hydroxypropylbenzophenone, acrylic benzophenone, 4,4'-bis(dimethylamino)benzoate, benzophenones such as 4,4'-dichlorobenzophenone, 4,4'-dichlorobenzophenone, etc.; thioxanthones such as thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, diethylthioxanthone, dimethylthioxanthone, etc.; acylphosphine oxides such as 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (BASF product name: Irgacure TPO), bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (BASF product name: Irgacure 819), etc.;Examples of the oxyphenylacetic acid, 2-[2-oxo-2-phenylacetoxyethoxy]ethyl ester and oxyphenylacetic acid, 2-(2-hydroxyethoxy)ethyl ester mixture (BASF product name: Irgacure 754), methyl benzoylformate (BASF product name: Irgacure MBF), α-acyloxime ester, benzyl-(o-ethoxycarbonyl)-α-monoxime, glyoxyester, 2-ethylanthraquinone, camphorquinone, tetramethylthiuram sulfide, azobisisobutyronitrile, benzoyl peroxide, dialkyl peroxide, tert-butyl peroxypivalate, etc.;

[0049] In consideration of solubility in water, ion balance and interaction with the monomer, it is preferable to select from 2,2'-azo(2-methyl-N-(2-hydroxyethyl)propionamide, 2,2'-azobis(N-(2-carboxyethyl)-2-methylpropionamidine) n-hydrate, 4,4'-azobis(4-cyanopentanoic acid), 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane]disulfate dihydrate, 2,2'-azobis[2-(2-imidazolin-2-yl)propane], 2,2'-azobis(2-amidinopropane)dihydrochloride and peroxodisulfuric acid. Considering the solubility in organic solvents, ion balance, and interaction with monomers, it is desirable to use 2,2'-azobis(2,4-dimethylvaleronitrile) or 2,2'-azobis(isobutyronitrile).

[0050] The amount of the polymerization initiator added is 0.05% by mass to 10% by mass based on the total mass of the monomer components used in the polymerization.

[0051] The reaction conditions are that the reaction vessel is heated to 50 to 200°C in an oil bath or the like, and the mixture is stirred for 1 to 48 hours, more preferably at 80 to 150°C for 5 to 30 hours, to progress the polymerization reaction and obtain the copolymer of the present invention. The reaction atmosphere is preferably a nitrogen atmosphere.

[0052] As for the reaction procedure, all the reactants may be placed in a reaction solvent at room temperature and then heated to the above temperature to polymerize, or the whole or part of the mixture of reactants may be added dropwise in small portions to a pre-heated solvent.

[0053] The weight average molecular weight of the copolymer according to the present invention may be several thousand to several million, preferably 5,000 to 5,000,000, more preferably 10,000 to 2,000,000. The copolymer may be a random copolymer, a block copolymer, or a graft copolymer, preferably a random copolymer. Furthermore, the copolymer produced in this manner is considered to be a three-dimensional polymer since it contains a bifunctional monomer, and is in a dissolved or dispersed state in a solution containing water or alcohol.

[0054] The coating film-forming composition according to the present invention may be prepared by isolating and purifying the copolymer thus obtained, and then diluting the copolymer with a desired solvent to a predetermined concentration. Furthermore, the coating film-forming composition according to the present invention may be prepared from a reaction solution (that is, a copolymer-containing varnish) obtained after the polymerization reaction.

[0055] Examples of the solvent contained in the coating film forming composition of the present invention include water, phosphate buffered saline (PBS), and alcohol. Examples of the alcohol include alcohols having 2 to 6 carbon atoms, such as ethanol, propanol, isopropanol, 1-butanol, 2-butanol, isobutanol, t-butanol, 1-pentanol, 2-pentanol, 3-pentanol, 1-heptanol, 2-heptanol, 2,2-dimethyl-1-propanol (=neopentyl alcohol), 2-methyl-1-propanol, 2-methyl-1-butanol, 2-methyl-2-butanol (=t-amyl alcohol), 3-methyl-1-butanol, 3-methyl-3-pentanol, cyclopentanol, 1-hexanol, 2-hexanol, 3-hexanol, 2,3-dimethyl-1-propanol, 2-methyl-1-butanol, 2-methyl-2-butanol (=t-amyl alcohol), 2-methyl-1-butanol, 2-methyl-3-pent ... Examples of suitable solvents include ethyl-2-butanol, 3,3-dimethyl-1-butanol, 3,3-dimethyl-2-butanol, 2-ethyl-1-butanol, 2-methyl-1-pentanol, 2-methyl-2-pentanol, 2-methyl-3-pentanol, 3-methyl-1-pentanol, 3-methyl-2-pentanol, 3-methyl-3-pentanol, 4-methyl-1-pentanol, 4-methyl-2-pentanol, 4-methyl-3-pentanol and cyclohexanol. These solvents may be used alone or in combination, but from the viewpoint of dissolving the copolymer, it is preferable to select from water, PBS, ethanol and propanol.

[0056] The concentration of solids in the coating film forming composition according to the present invention is preferably 0.01 to 50% by mass in order to form a uniform coating film. The concentration of the copolymer in the coating film forming composition is preferably 0.01 to 5% by mass, more preferably 0.01 to 4% by mass, and particularly preferably 0.01 to 3% by mass. If the concentration of the copolymer is 0.01% by mass or less, the concentration of the copolymer in the obtained coating film forming composition is too low to form a coating film with a sufficient thickness, and if it is 5% by mass or more, the storage stability of the coating film forming composition is deteriorated, and precipitation or gelation of the dissolved matter may occur.

[0057] Furthermore, in addition to the copolymer and the solvent, the composition for forming a coating film of the present invention may contain other substances as required within the range that does not impair the performance of the resulting coating film. Examples of other substances include preservatives, surfactants, primers that improve adhesion to the substrate, antifungal agents, and sugars.

[0058] In order to adjust the ion balance of the copolymer in the coating film forming composition according to the present invention, the coating film of the present invention may further include a step of preliminarily adjusting the pH of the coating film forming composition. The pH adjustment may be performed, for example, by adding a pH adjuster to a composition containing the copolymer and a solvent, and adjusting the pH of the composition to 2 to 13.5, preferably 2 to 8.5, more preferably 3 to 8, or preferably 8.5 to 13.5, more preferably 10 to 13.5. The type and amount of the pH adjuster that can be used are appropriately selected depending on the concentration of the copolymer, the ratio of anion to cation, and the like. Examples of pH adjusters include organic amines such as ammonia, diethanolamine, pyridine, N-methyl-D-glucamine, and tris(hydroxymethyl)aminomethane; alkali metal hydroxides such as potassium hydroxide and sodium hydroxide; alkali metal halides such as potassium chloride and sodium chloride; inorganic acids such as sulfuric acid, phosphoric acid, hydrochloric acid, and carbonic acid, or alkali metal salts thereof; quaternary ammonium cations such as choline, or mixtures thereof (e.g., buffer solutions such as phosphate buffered saline).Among these, ammonia, diethanolamine, sodium hydroxide, choline, N-methyl-D-glucamine, and tris(hydroxymethyl)aminomethane are preferred, and ammonia, diethanolamine, sodium hydroxide, and choline are particularly preferred.

[0059] (Coating film)

[0060] The coating film of the present invention can be formed by applying the composition for forming a coating film of the present invention to a substrate and drying it.

[0061] The substrate material for forming the coating film of the present invention may be glass, a metal-containing compound or a metalloid-containing compound, activated carbon, or a resin. Examples of the metal-containing compound or the metalloid-containing compound include ceramics, which are sintered bodies whose basic component is a metal oxide and are sintered by heat treatment at high temperatures, inorganic solid materials such as molded bodies of inorganic compounds such as semiconductors such as silicon, metal oxides or metalloid oxides (silicon oxide, alumina, etc.), metal carbides or metalloid carbides, metal nitrides or metalloid nitrides (silicon nitride, etc.), and metal borides or metalloid borides, aluminum, nickel titanium, and stainless steel (SUS304, SUS316, SUS316L, etc.).

[0062] The resin may be either a natural resin or a synthetic resin. Natural resins include cellulose, cellulose triacetate (CTA), and cellulose immobilized with dextran sulfate. Synthetic resins include polyacrylonitrile (PAN), polyester polymer alloy (PEPA), polystyrene (PS), polysulfone (PSF), polyethylene terephthalate (PET), polymethyl methacrylate (PMMA), polyvinyl alcohol (PVA), polyurethane (PU), ethylene vinyl alcohol (EVAL), polyethylene (PE), polyester (PE), polypropylene (PP), polyvinylidene fluoride (PVDF), polyethersulfone (PES), and polycarbonate. Polyvinyl chloride (PC), polyvinyl chloride (PVC), polytetrafluoroethylene (PTFE), ultra-high molecular weight polyethylene (UHPE), polydimethylsiloxane (PDMS), acrylonitrile-butadiene-styrene resin (ABS), Teflon (registered trademark), cycloolefin polymer (COP) (e.g., ZEONOR (registered trademark), ZEONEX (registered trademark) (manufactured by Zeon Corporation)) or various ion exchange resins are preferably used, but polystyrene (PS), polyethersulfone (PES), polypropylene (PP) and cycloolefin polymer (COP) are more preferred, with polystyrene (PS) and polyethersulfone (PES) being particularly preferred. The coating film of the present invention can be formed by low-temperature drying, and is therefore also applicable to resins with low heat resistance.

[0063] The form of the substrate of the present invention is not particularly limited, and examples thereof include fibers, particles, gel forms, and porous forms, and the shape may be a flat plate or a curved surface.

[0064] In order to form the coating film of the present invention, the above-mentioned composition for forming a coating film is applied to at least a part of the surface of a substrate. The coating method is not particularly limited, and a typical coating method such as spin coating, dip coating, solvent casting, etc. can be used.

[0065] The drying step of the coating film according to the present invention is carried out in air or vacuum, preferably at a temperature within the range of −200 to 200° C. It is considered that the drying step removes the solvent in the composition for forming a coating film, and the anionic group and cationic group of the compound of formula (1) and formula (2) of the copolymer according to the present invention form ionic bonds to completely fix the composition to the substrate.

[0066] The coating film can be formed by drying at room temperature (10 to 35°C, e.g., 25°C), but in order to form the coating film more quickly, it may be dried at, for example, 40 to 80°C. A drying process at extremely low to low temperatures (around -200 to -30°C) using the freeze-drying method may also be used. Freeze-drying is called vacuum freeze-drying, and is a method in which the material to be dried is usually cooled with a refrigerant and the solvent is removed by sublimation in a vacuum state. Common refrigerants used in freeze-drying include a mixture of dry ice and methanol (-78°C), liquid nitrogen (-196°C), etc.

[0067] If the drying temperature is below -200°C, an uncommon refrigerant must be used, resulting in lack of versatility, and drying takes a long time due to solvent sublimation, resulting in poor efficiency. If the drying temperature is above 200°C, the ionic bond reaction on the coating film surface proceeds too much, causing the surface to lose hydrophilicity, and the ability to inhibit adhesion of biological materials is not exerted. The drying temperature is more preferably 10 to 180°C, and even more preferably 25 to 150°C.

[0068] After drying, in order to remove impurities, unreacted monomers, etc. remaining on the coating film, and further to adjust the ion balance of the copolymer in the film, a step of washing with at least one solvent selected from water and an aqueous solution containing an electrolyte may be carried out. Washing is preferably performed with running water or ultrasonic washing. The aqueous solution containing water and an electrolyte may be heated, for example, in the range of 40 to 95°C. The aqueous solution containing an electrolyte is preferably PBS, saline (containing only sodium chloride), Dulbecco's phosphate buffered saline, Tris buffered saline, HEPES buffered saline, and Veronal buffered saline, and PBS is particularly preferred. After adhesion, the coating film remains firmly attached to the substrate without being eluted even when washed with water, PBS, alcohol, etc. Even if a biological material adheres to the formed coating film, it can be easily removed by washing with water, etc., and the substrate surface on which the coating film of the present invention is formed has the ability to inhibit adhesion of biological material.

[0069] The coating film of the present invention has a thickness of preferably 10 to 1000 Å, more preferably 10 to 500 Å, and further preferably 30 to 500 Å.

[0070] If necessary, sterilization may be performed using gamma rays, ethylene oxide, an autoclave, or the like.

[0071] The coating film of the present invention has the ability to inhibit adhesion of biological materials, and therefore can be suitably used as a coating film for medical substrates. Therefore, specific embodiments of the substrate include, for example, leukocyte removal filters, blood transfusion filters, virus removal filters, microclot removal filters, blood purification modules, artificial hearts, artificial lungs, blood circuits, artificial blood vessels, blood vessel bypass tubes, medical tubes, artificial valves, cannulas, stents, catheters, intravascular carutes, balloon catheters, guide wires, sutures, indwelling needles, shunts, artificial joints, artificial hip joints, blood bags, blood storage containers, surgical auxiliary instruments, adhesion prevention membranes, wound dressings, etc. Here, the blood purification module refers to a module that has the function of circulating blood outside the body and removing waste products and harmful substances from the blood, and examples thereof include artificial kidneys, toxin adsorption filters and columns. For example, a filter for an artificial dialyzer having the coating membrane of the present invention can be produced by passing the composition for forming the coating membrane of the present invention through the inside of a hollow fiber-shaped filter made of the above-mentioned material and having a diameter of, for example, 0.1 to 500 μm, followed by a drying process and a washing process (washing with hot water (for example, 40 to 95° C.)).

[0072] Other specific embodiments of the substrate include cell culture vessels such as flasks, dishes, and plates, various research instruments suppressing protein adhesion, diagnostic drug devices for biochemical research, etc. That is, the composition for forming a coating film of the present invention is also useful as a blocking agent for suppressing nonspecific adsorption in enzyme-linked immunosorbent assay (ELISA) and latex agglutination methods that are widely used in clinical diagnostic methods, and as a stabilizer for stabilizing proteins such as enzymes and antibodies. Further specific embodiments of the substrate include toiletries, personal care products, cosmetics, contact lens care products, and the like. EXAMPLES

[0073] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples in any way.

[0074] <Method for measuring monomer purity> The absolute mass % (purity) of acid phosphooxy polypropylene glycol monomethacrylate (average number of moles of propylene oxide added: 5) (product name: PPM-5P, manufactured by Toho Chemical Industry Co., Ltd.) used in the following synthesis examples is: 31 The composition of the phosphorus-containing compound was analyzed using P-NMR measurement, and the molecular weight was calculated by converting the number of moles of acid phosphooxy polypropylene glycol monomethacrylate (average number of moles of propylene oxide added: 5) to 5. ( 31 P-NMR measurement conditions) ·Device:AVANCE III HD(500MHz) Solvent: deuterated acetone ·Measurement temperature: room temperature (23℃) Measurement conditions: Non-decoupling method Measurement data points: 131072 (128k) Pulse width: 90° pulse (14μsec.) Measurement range: -50~10ppm Number of times: 256

[0075] <Method for measuring molecular weight of copolymer> The weight average molecular weight of the copolymer shown in the following synthesis examples is the result of measurement by gel filtration chromatography (hereinafter abbreviated as GFC). (GFC measurement conditions) Equipment: HLC-8320GPC (Tosoh Corporation) or LC-20AD (Shimadzu Corporation) GFC column: TSKgel GMPWXL (7.8mm ID x 30cm) x 2-3 Eluent: Aqueous solution containing ionic substances or a mixture of EtOH (ethanol) Column temperature: 40℃ Detector: RI Injection concentration: polymer solids 0.05-0.5% ·Injection volume: 10μL~100μL Calibration curve: Cubic approximation curve Standard sample: Polyethylene oxide or sodium polystyrene sulfonate

[0076] <Synthesis Example 1> 10.59g of ethanol was added to 1.38g of acid phosphooxy polypropylene glycol monomethacrylate (average number of moles of propylene oxide added: 5) (product name: PPM-5P, manufactured by Toho Chemical Industry Co., Ltd., absolute mass% (purity) 97.3 mass%), and dissolved thoroughly. Next, 0.46g of 2-(dimethylamino)ethyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.10g of polyethylene glycol dimethacrylate (average number of moles of polyethylene glycol added: 4) (product name: Blenmar (registered trademark) PDE-200, manufactured by NOF Corporation) (mass% relative to the entire copolymer: 5.2 mass%), and 7.03g of pure water were added and thoroughly stirred. 9.6mg of dimethyl 1,1'-azobis(1-cyclohexanecarboxylate) (product name: VE-073, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added. The 100 mL flask containing the mixed solution containing all of the above, which had been thoroughly stirred to make it uniform, was replaced with nitrogen and heated to the reflux temperature while stirring (oil bath temperature: set to 95°C). The above environment was maintained for 24 hours with heating and stirring to obtain a copolymer-containing varnish with a solid content of approximately 11.52% by mass. The weight average molecular weight of the resulting liquid in GFC was approximately 440,000.

[0077] <Synthesis Example 2> 11.31 g of ethanol was added to 1.40 g of acid phosphooxy polypropylene glycol monomethacrylate (average number of moles of propylene oxide added: 5) (product name: PPM-5P, manufactured by Toho Chemical Industry Co., Ltd., absolute mass% (purity) 97.3 mass%), and dissolved thoroughly. Next, 0.47 g of 2-(dimethylamino)ethyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.23 g of polyethylene glycol dimethacrylate (average number of moles of polyethylene glycol added: 4) (product name: Blenmar (registered trademark) PDE-200, manufactured by NOF Corporation) (mass% relative to the entire copolymer: 11.0 mass%), and 7.62 g of pure water were added and thoroughly stirred. 10.5 mg of dimethyl 1,1'-azobis(1-cyclohexanecarboxylate) (product name: VE-073, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added. The 100 mL flask containing the mixed solution containing all of the above, which had been thoroughly stirred to make it uniform, was replaced with nitrogen and heated to the reflux temperature while stirring (oil bath temperature: set to 95°C). The above environment was maintained for 24 hours while heating and stirring to obtain a copolymer-containing varnish with a solid content of approximately 10.52% by mass. The weight average molecular weight of the resulting liquid in GFC was approximately 610,000.

[0078] <Synthesis Example 3> Acid phosphooxy polypropylene glycol monomethacrylate (average number of moles of propylene oxide added: 5) (product name: PPM-5P, manufactured by Toho Chemical Industry Co., Ltd., absolute mass% (purity) 97.3 mass%) 5.0 g polyethylene glycol dimethacrylate (average number of moles of polyethylene glycol added: 4) (product name: Blenmar (registered trademark) PDE-200, manufactured by NOF Corp.) 1.8 g (mass% relative to the entire copolymer: 21.2 mass%), 2-(dimethylamino)ethyl methacrylate (manufactured by Mitsubishi Gas Chemical Co., Ltd.) 1.7 g, dimethyl-1,1'-azobis(1-cyclohexanecarboxylate) (product name: VE-073, manufactured by Fujifilm Wako Pure Chemical Industries Co., Ltd.) 42.7 mg, ethanol (manufactured by Kanto Chemical Co., Ltd.) 18.5 g was added and stirred uniformly to prepare a mixed solution. Separately, 30.9 g of ion-exchanged water and 27.8 g of ethanol (Kanto Chemical Co., Ltd.) were added to a three-neck flask equipped with a cooling tube, and the temperature was raised to the reflux temperature while stirring. While maintaining this state, the above mixture was dropped into boiling ion-exchanged water over 1 hour using a dropping pump connected to a Teflon (registered trademark) tube. After dropping, the mixture was heated and stirred for 23 hours while maintaining the above environment. After the reaction was completed, the mixture was cooled to obtain 58 g of a copolymer-containing solution with a solid content of about 9.75% by mass. The weight average molecular weight of the obtained liquid in GFC was about 300,000.

[0079] <Synthesis Example 4> Acid phosphooxy polypropylene glycol monomethacrylate (average number of moles of propylene oxide added: 5) (product name: PPM-5P, manufactured by Toho Chemical Industry Co., Ltd., absolute mass% (purity) 97.3 mass%) 3.4 g of polyethylene glycol dimethacrylate (average number of moles of polyethylene glycol added: 4) (product name: Blenmar (registered trademark) PDE-200, manufactured by NOF Corp.) 2.1 g (mass% relative to the entire copolymer: 31.3 mass%), 2-(dimethylamino)ethyl methacrylate (manufactured by Mitsubishi Gas Chemical Co., Ltd.) 1.2 g, dimethyl-1,1'-azobis(1-cyclohexanecarboxylate) (product name: VE-073, manufactured by Fujifilm Wako Pure Chemical Industries Co., Ltd.) 33.4 mg was added to ethanol (manufactured by Kanto Chemical Co., Ltd.) 24.2 g and stirred uniformly to prepare a mixed solution. Separately, 24.2 g of ion-exchanged water and 12.1 g of ethanol (Kanto Chemical Co., Ltd.) were added to a three-neck flask equipped with a cooling tube, and the temperature was raised to the reflux temperature while stirring. While maintaining this state, the above mixture was dropped into boiling ion-exchanged water over 1 hour using a dropping pump connected to a Teflon (registered trademark) tube. After dropping, the mixture was heated and stirred for 23 hours while maintaining the above environment. After the reaction was completed, the mixture was cooled to obtain 55 g of a copolymer-containing solution with a solid content of about 10.43% by mass. The weight average molecular weight of the obtained liquid in GFC was about 320,000.

[0080] <Synthesis Example 5> Acid phosphooxy polypropylene glycol monomethacrylate (average added mole number of propylene oxide: 5) (product name: PPM-5P, manufactured by Toho Chemical Industry Co., Ltd., absolute mass% (purity) 97.3 mass%) 4.0 g, ethylene glycol dimethacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) 0.39 g (mass% relative to the entire copolymer: 6.7 mass%), 2-(dimethylamino)ethyl methacrylate (manufactured by Mitsubishi Gas Chemical Co., Ltd.) 1.4 g, dimethyl-1,1'-azobis(1-cyclohexanecarboxylate) (product name; VE-073, manufactured by Fujifilm Wako Pure Chemical Industries Co., Ltd.) 0.17 g, ethanol (manufactured by Kanto Chemical Co., Ltd.) 21.4 g was added to the mixture and stirred uniformly to prepare a mixed solution. Meanwhile, 21.4 g of ion-exchanged water and 10.7 g of ethanol (manufactured by Kanto Chemical Co., Ltd.) were added to a three-neck flask equipped with a cooling tube, and the temperature was raised to the reflux temperature while stirring. While maintaining this state, the mixture was dropped into boiling ion-exchanged water over 1 hour using a dropping pump connected to a Teflon (registered trademark) tube. After dropping, the mixture was heated and stirred for 23 hours while maintaining the above environment. After the reaction was completed, the mixture was cooled to obtain 50 g of a copolymer-containing solution with a solid content of approximately 9.91% by mass. The weight average molecular weight of the obtained liquid in GFC was approximately 230,000.

[0081] <Synthesis Example 6> Acid phosphooxy polypropylene glycol monomethacrylate (average added mole number of propylene oxide: 5) (product name: PPM-5P, manufactured by Toho Chemical Industry Co., Ltd., absolute mass% (purity) 97.3 mass%) 2.47 g, triethylene glycol dimethacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) 0.57 g (mass% relative to the entire copolymer: 15.6 mass%), 2-(dimethylamino)ethyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) 0.62 g, dimethyl-1,1′-azobis(1-cyclohexanecarboxylate) (product name: VE-073, manufactured by Fujifilm Wako Pure Chemical Industries Co., Ltd.) 19.1 mg, was added with 6.5 g of isopropyl alcohol (manufactured by Junsei Chemical Co., Ltd.) and 10.0 g of pure water and stirred uniformly to prepare a mixed solution. Separately, 9.7 g of pure water and 6.6 g of isopropyl alcohol (Junsei Chemical Co., Ltd.) were added to a three-neck flask equipped with a condenser and heated to the reflux temperature while stirring. While maintaining this state, the above mixture was dripped into the boiling liquid in the lower layer using a dropping funnel over 1 hour. After dripping, the mixture was heated and stirred for 23 hours while maintaining the above environment. After the reaction was completed, the mixture was cooled to obtain a copolymer-containing solution with a solid content of approximately 13.16 mass%. The weight average molecular weight of the obtained liquid in GFC was approximately 83,000.

[0082] <Synthesis Example 7> 20.01 g of ethanol was added to 2.28 g of acid phosphooxy polypropylene glycol monomethacrylate (average number of moles of propylene oxide added: 5) (product name: PPM-5P, manufactured by Toho Chemical Industry Co., Ltd., absolute mass% (purity) 97.3 mass%), and dissolved thoroughly. Next, 1.03 g of methacryloylcholine chloride 80% aqueous solution (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.37 g of polyethylene glycol dimethacrylate (average number of moles of polyethylene glycol added: 4) (product name: Blenmar (registered trademark) PDE-200, manufactured by NOF Corporation) (mass% relative to the entire copolymer: 10.7 mass%), and 13.38 g of pure water were added and thoroughly stirred. 18.4 mg of dimethyl 1,1'-azobis(1-cyclohexanecarboxylate) (product name: VE-073, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added. The 100 mL flask containing the mixed solution containing all of the above, which had been thoroughly stirred to make it uniform, was replaced with nitrogen and heated to the reflux temperature while stirring. The above environment was maintained for 24 hours with heating and stirring to obtain a copolymer-containing varnish with a solid content of approximately 9.39% by mass. The weight average molecular weight of the resulting liquid in GFC was approximately 140,000.

[0083] <Synthesis Example 8> Acid phosphooxy polypropylene glycol monomethacrylate (average added mole number of propylene oxide: 5) (product name: PPM-5P, manufactured by Toho Chemical Industry Co., Ltd., absolute mass% (purity) 97.3 mass%) 3.5 g ethylene glycol dimethacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) 0.34 g (mass% relative to the entire copolymer: 6.3 mass%), methacryloylcholine chloride 80% aqueous solution (manufactured by Tokyo Chemical Industry Co., Ltd.) 2.0 g, dimethyl-1,1'-azobis (1-cyclohexane carboxylate) (product name; VE-073, manufactured by Fujifilm Wako Pure Chemical Industries Co., Ltd.) 29.1 mg was added to ethanol (manufactured by Kanto Chemical Co., Ltd.) 21.1 g and stirred uniformly to prepare a mixed solution. Meanwhile, 21.1 g of ion-exchanged water and 10.5 g of ethanol (manufactured by Kanto Chemical Co., Ltd.) were added to a three-neck flask equipped with a cooling tube, and the temperature was raised to the reflux temperature while stirring. While maintaining this state, the mixture was dropped into boiling ion-exchanged water over 1 hour using a dropping pump connected to a Teflon (registered trademark) tube. After dropping, the mixture was heated and stirred for 23 hours while maintaining the above environment. After the reaction was completed, the mixture was cooled to obtain 48 g of a copolymer-containing solution with a solid content of about 9.56 mass%. The weight average molecular weight of the obtained liquid in GFC was about 36,000.

[0084] <Synthesis Example 9> Acid phosphooxy polypropylene glycol monomethacrylate (average number of moles of propylene oxide added: 5) (product name: PPM-5P, manufactured by Toho Chemical Industry Co., Ltd., absolute mass% (purity) 97.3 mass%) 1.37 g of polyethylene glycol dimethacrylate (average number of moles of polyethylene glycol added: 4) (product name: Blenmar (registered trademark) PDE-200, manufactured by NOF Corp.) 0.52 g (mass% relative to the entire copolymer: 18.8 mass%), 2-methacryloyloxyethyl phosphorylcholine (MPC, manufactured by Tokyo Chemical Industry Co., Ltd.) 0.88 g, dimethyl-1,1'-azobis (1-cyclohexane carboxylate) (product name: VE-073, manufactured by Fujifilm Wako Pure Chemical Industries Co., Ltd.) 12.4 mg was added with 6.09 g of ethanol (manufactured by Kanto Chemical Co., Ltd.) and 6.08 g of pure water and stirred uniformly to prepare a mixed solution. Separately, 6.42 g of pure water and 6.55 g of ethanol (Kanto Chemical Co., Ltd.) were added to a three-neck flask equipped with a condenser and heated to the reflux temperature while stirring. While maintaining this state, the above mixture was dropped into the boiling liquid in the lower layer using a dropping funnel over 1 hour. After dropping, the mixture was heated and stirred for 23 hours while maintaining the above environment. After the reaction was completed, the mixture was cooled to obtain a copolymer-containing solution with a solid content of approximately 16.31% by mass. The weight average molecular weight of the obtained liquid in GFC was approximately 520,000.

[0085] <Synthesis Example 10> Acid phosphooxy polypropylene glycol monomethacrylate (average number of moles of propylene oxide added: 5) (product name: PPM-5P, manufactured by Toho Chemical Industry Co., Ltd., absolute mass% (purity) 97.3 mass%) 0.28 g polyethylene glycol dimethacrylate (average number of moles of polyethylene glycol added: 4) (product name: Blenmar (registered trademark) PDE-200, manufactured by NOF Corp.) 0.61 g (mass% relative to the entire copolymer: 24.4 mass%), 2-methacryloyloxyethyl phosphorylcholine (MPC, manufactured by Tokyo Chemical Industry Co., Ltd.) 1.61 g, dimethyl-1,1'-azobis (1-cyclohexane carboxylate) (product name: VE-073, manufactured by Fujifilm Wako Pure Chemical Industries Co., Ltd.) 10.4 mg was added with 5.62 g of ethanol (manufactured by Kanto Chemical Co., Ltd.) and 5.60 g of pure water and stirred uniformly to prepare a mixed solution. Separately, 5.16 g of pure water and 5.00 g of ethanol (Kanto Chemical Co., Ltd.) were added to a three-neck flask equipped with a condenser and heated to the reflux temperature while stirring. While maintaining this state, the above mixture was dropped into the boiling liquid in the lower layer using a dropping funnel over 1 hour. After dropping, the mixture was heated and stirred for 23 hours while maintaining the above environment. After the reaction was completed, the mixture was cooled to obtain a copolymer-containing solution with a solid content of about 14.25% by mass. The weight average molecular weight of the obtained liquid in GFC was about 300,000.

[0086] <Synthesis Example 11> Acid phosphooxy polypropylene glycol monomethacrylate (average number of moles of propylene oxide added: 5) (product name: PPM-5P, manufactured by Toho Chemical Industry Co., Ltd., absolute mass% (purity) 97.3 mass%) 1.52 g, methacryloylcholine chloride about 80% aqueous solution (manufactured by Tokyo Chemical Industry Co., Ltd.) 0.64 g, butyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) 0.61 g, ethylene glycol dimethacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) 0.61 g (mass% relative to the entire copolymer: 18.7 mass%), ethanol (manufactured by Kanto Chemical Co., Ltd.) 14.5 g, dimethyl-1,1'-azobis(1-cyclohexanecarboxylate) (product name: VE-073, manufactured by Fujifilm Wako Pure Chemical Industries Co., Ltd.) 18.2 mg were added and stirred uniformly to prepare a mixed solution. Meanwhile, 14.5 g of ethanol (Kanto Chemical Co., Ltd.) was added to a four-neck flask equipped with a cooling tube, the atmosphere in the flask was replaced with nitrogen, and the temperature was raised to the reflux temperature while stirring. While maintaining this state, the above-mentioned mixed liquid was added dropwise over 1 hour, and after the addition, the mixture was heated and stirred while maintaining the above-mentioned environment for 24 hours. After the reaction was completed, the mixture was cooled to obtain a copolymer-containing solution with a solid content of about 12.1% by mass. The weight average molecular weight of the obtained liquid in GFC was about 220,000.

[0087] <Synthesis Example 12> The copolymer-containing liquid obtained in Synthesis Example 11 was reprecipitated in hexane, a poor solvent, and the precipitate was collected by filtration and dried under reduced pressure. The weight average molecular weight of the obtained powder in GFC was about 230,000.

[0088] <Synthesis Example 13> Acid phosphooxy polypropylene glycol monomethacrylate (average number of moles of propylene oxide added: 5) (product name: PPM-5P, manufactured by Toho Chemical Industry Co., Ltd., absolute mass% (purity) 97.3 mass%) 1.50 g, methacryloylcholine chloride about 80% aqueous solution (manufactured by Tokyo Chemical Industry Co., Ltd.) 0.64 g, butyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) 0.52 g, ethylene glycol dimethacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) 0.74 g (mass% relative to the entire copolymer: 22.6 mass%), ethanol (manufactured by Kanto Chemical Co., Ltd.) 14.7 g, dimethyl-1,1'-azobis(1-cyclohexanecarboxylate) (product name: VE-073, manufactured by Fujifilm Wako Pure Chemical Industries Co., Ltd.) 17.8 mg were added and stirred uniformly to prepare a mixed solution. Meanwhile, 14.5 g of ethanol (Kanto Chemical Co., Ltd.) was added to a four-neck flask equipped with a cooling tube, the atmosphere in the flask was replaced with nitrogen, and the temperature was raised to the reflux temperature while stirring. While maintaining this state, the above-mentioned mixed liquid was added dropwise over 1 hour, and after the addition, the mixture was heated and stirred while maintaining the above-mentioned environment for 24 hours. After the reaction was completed, the mixture was cooled to obtain a copolymer-containing solution with a solid content of about 10.4 mass%. The weight average molecular weight of the obtained liquid in GFC was about 170,000.

[0089] <Synthesis Example 14> The copolymer-containing liquid obtained in Synthesis Example 13 was reprecipitated in hexane, a poor solvent, and the precipitate was collected by filtration and dried under reduced pressure. The weight average molecular weight of the obtained powder in GFC was about 170,000.

[0090] <Synthesis Example 15> Acid phosphooxy polypropylene glycol monomethacrylate (average number of moles of propylene oxide added: 5) (product name: PPM-5P, manufactured by Toho Chemical Industry Co., Ltd., absolute mass% (purity) 97.3 mass%) 2.00 g, methacryloylcholine chloride about 80% aqueous solution (manufactured by Tokyo Chemical Industry Co., Ltd.) 0.85 g, butyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) 0.57 g, ethylene glycol dimethacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) 1.12 g (mass% relative to the entire copolymer: 25.6 mass%), ethanol (manufactured by Kanto Chemical Co., Ltd.) 19.8 g, dimethyl-1,1'-azobis(1-cyclohexanecarboxylate) (product name: VE-073, manufactured by Fujifilm Wako Pure Chemical Industries Co., Ltd.) 23.9 mg were added and stirred uniformly to prepare a mixed solution. Meanwhile, 19.8 g of ethanol (Kanto Chemical Co., Ltd.) was added to a four-neck flask equipped with a cooling tube, the atmosphere in the flask was replaced with nitrogen, and the temperature was raised to the reflux temperature while stirring. While maintaining this state, the above-mentioned mixed liquid was added dropwise over 1 hour, and after the addition, the mixture was heated and stirred while maintaining the above-mentioned environment for 24 hours. After the reaction was completed, the mixture was cooled to obtain a copolymer-containing solution with a solid content of about 9.9% by mass. The weight average molecular weight of the obtained liquid in GFC was about 260,000.

[0091] <Synthesis Example 16> Acid phosphooxy polypropylene glycol monomethacrylate (average number of moles of propylene oxide added: 5) (product name: PPM-5P, manufactured by Toho Chemical Industry Co., Ltd., absolute mass% (purity) 97.3 mass%) 2.02 g, methacryloylcholine chloride about 80% aqueous solution (manufactured by Tokyo Chemical Industry Co., Ltd.) 0.85 g, butyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) 0.46 g, ethylene glycol dimethacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) 1.29 g (mass% relative to the entire copolymer: 29.0 mass%), ethanol (manufactured by Kanto Chemical Co., Ltd.) 20.0 g, dimethyl-1,1'-azobis(1-cyclohexanecarboxylate) (product name: VE-073, manufactured by Fujifilm Wako Pure Chemical Industries Co., Ltd.) 25.3 mg were added and stirred uniformly to prepare a mixed solution. Meanwhile, 20.0 g of ethanol (Kanto Chemical Co., Ltd.) was added to a four-neck flask equipped with a cooling tube, the atmosphere in the flask was replaced with nitrogen, and the temperature was raised to the reflux temperature while stirring. While maintaining this state, the above-mentioned mixed liquid was added dropwise over 1 hour, and after the addition, the mixture was heated and stirred while maintaining the above-mentioned environment for 24 hours. After the reaction was completed, the mixture was cooled to obtain a copolymer-containing solution with a solid content of about 10.1% by mass. The weight average molecular weight of the obtained liquid in GFC was about 260,000.

[0092] <Synthesis Example 17> The copolymer-containing liquid obtained in Synthesis Example 16 was reprecipitated in hexane, a poor solvent, and the precipitate was collected by filtration and dried under reduced pressure. The weight average molecular weight of the obtained powder in GFC was about 260,000.

[0093] <Comparative Synthesis Example 1> 16.70 g of ethanol was added to 2.27 g of acid phosphooxy polypropylene glycol monomethacrylate (average number of moles of propylene oxide added: 5) (product name: PPM-5P, manufactured by Toho Chemical Industry Co., Ltd., absolute mass% (purity) 97.3 mass%), and dissolved thoroughly. Next, 0.80 g of 2-(dimethylamino)ethyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) and 11.23 g of pure water were added and stirred thoroughly. 15.7 mg of dimethyl 1,1'-azobis(1-cyclohexanecarboxylate) (product name: VE-073, manufactured by Fujifilm Wako Pure Chemical Industries Co., Ltd.) was added. The inside of a 100 mL flask containing the mixed solution containing all of the above, which had been thoroughly stirred to become homogenous, was replaced with nitrogen, and the temperature was raised to the reflux temperature while stirring (oil bath temperature: set to 95 ° C). By heating and stirring while maintaining the above environment for 24 hours, a copolymer-containing varnish with a solid content of about 10.60 mass% was obtained. The weight average molecular weight of the resulting liquid in GFC was about 310,000.

[0094] <Comparative Synthesis Example 2> Acid phosphooxy polypropylene glycol monomethacrylate (average number of moles of propylene oxide added: 5) (product name: PPM-5P, manufactured by Toho Chemical Industry Co., Ltd., absolute mass% (purity) 97.3 mass%) 2.8 g polyethylene glycol dimethacrylate (average number of moles of polyethylene glycol added: 4) (product name: Blenmar (registered trademark) PDE-200, manufactured by NOF Corp.) 2.7 g (mass% relative to the entire copolymer: 41.5 mass%), dimethylaminoethyl methacrylate (manufactured by Mitsubishi Gas Chemical Co., Ltd.) 1.0 g, dimethyl-1,1'-azobis (1-cyclohexane carboxylate) (product name: VE-073, manufactured by Fujifilm Wako Pure Chemical Industries Co., Ltd.) 32.3 mg was added to ethanol (manufactured by Kanto Chemical Co., Ltd.) 23.4 g was added and stirred uniformly to prepare a mixed solution. Separately, 23.4 g of ion-exchanged water and 11.7 g of ethanol (Kanto Chemical Co., Ltd.) were added to a three-neck flask equipped with a cooling tube, and the temperature was raised to the reflux temperature while stirring. While maintaining this state, the above mixture was dropped into boiling ion-exchanged water over 1 hour using a dropping pump connected to a Teflon (registered trademark) tube. After the dropping was completed, the mixture was heated and stirred while maintaining the above environment for 2 hours, and it was confirmed that gelation had occurred.

[0095] <Comparative Synthesis Example 3> 11.55g of ethanol was added to 1.37g of acid phosphooxy polypropylene glycol monomethacrylate (average number of moles of propylene oxide added: 5) (product name: PPM-5P, manufactured by Toho Chemical Industry Co., Ltd., absolute mass% (purity) 97.3 mass%), and dissolved thoroughly. Next, 0.49g of 2-(dimethylamino)ethyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.30g of polyethylene glycol monomethacrylate (average number of moles of polyethylene glycol added: 8) (product name: Blenmar (registered trademark) PE-350, manufactured by NOF Corporation) (mass% relative to the entire copolymer: 13.9 mass%), and 7.76g of pure water were added and thoroughly stirred. 10.7mg of dimethyl 1,1'-azobis(1-cyclohexanecarboxylate) (product name: VE-073, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added. The 100 mL flask containing the mixed solution containing all of the above, which had been thoroughly stirred to make it uniform, was replaced with nitrogen and heated to the reflux temperature while stirring (oil bath temperature: set to 95°C). The above environment was maintained for 24 hours with heating and stirring to obtain a copolymer-containing varnish with a solid content of approximately 10.26% by mass. The weight average molecular weight of the resulting liquid in GFC was approximately 410,000.

[0096] <Comparative Synthesis Example 4> 13.57g of ethanol was added to 1.83g of acid phosphooxy polypropylene glycol monomethacrylate (average number of moles of propylene oxide added: 5) (product name: PPM-5P, manufactured by Toho Chemical Industry Co., Ltd., absolute mass% (purity) 97.3 mass%), and dissolved thoroughly. Next, 1.18g of 2-methacryloyloxyethyl phosphorylcholine (MPC, manufactured by Tokyo Chemical Industry Co., Ltd.) and 13.56g of pure water were added and stirred thoroughly. 15.1mg of dimethyl 1,1'-azobis(1-cyclohexanecarboxylate) (product name: VE-073, manufactured by Fujifilm Wako Pure Chemical Industries Co., Ltd.) was added. The inside of a 100mL flask containing the mixed solution containing all of the above, which had been thoroughly stirred to become homogenous, was replaced with nitrogen, and the temperature was raised to the reflux temperature while stirring. The above environment was maintained for 24 hours, and a copolymer-containing varnish with a solid content of about 9.94% by mass was obtained by heating and stirring. The weight average molecular weight of the resulting liquid in GFC was about 590,000.

[0097] <Comparative Synthesis Example 5> 15.75g of ethanol was added to 1.37g of acid phosphooxy polypropylene glycol monomethacrylate (average number of moles of propylene oxide added: 5) (product name: PPM-5P, manufactured by Toho Chemical Industry Co., Ltd., absolute mass% (purity) 97.3 mass%), and dissolved thoroughly. Next, 2.10g of 2-methacryloyloxyethyl phosphorylcholine (MPC, manufactured by Tokyo Chemical Industry Co., Ltd.) and 15.76g of pure water were added and stirred thoroughly. 17.6mg of dimethyl 1,1'-azobis(1-cyclohexanecarboxylate) (product name: VE-073, manufactured by Fujifilm Wako Pure Chemical Industries Co., Ltd.) was added. The inside of a 100mL flask containing the mixed solution containing all of the above, which had been thoroughly stirred to become homogenous, was replaced with nitrogen, and the temperature was raised to the reflux temperature while stirring. The above environment was maintained for 24 hours, and a copolymer-containing varnish with a solid content of about 9.94 mass% was obtained by heating and stirring. The weight average molecular weight of the resulting liquid in GFC was about 150,000.

[0098] <Comparative Synthesis Example 6> Acid phosphooxy polypropylene glycol monomethacrylate (average number of moles of propylene oxide added: 5) (product name: PPM-5P, manufactured by Toho Chemical Industry Co., Ltd., absolute mass% (purity) 97.3 mass%) 1.84 g, methacryloylcholine chloride about 80% aqueous solution (manufactured by Tokyo Chemical Industry Co., Ltd.) 0.84 g, ethanol (manufactured by Kanto Chemical Co., Ltd.) 14.4 g, pure water 9.6 g, dimethyl-1,1'-azobis (1-cyclohexane carboxylate) (product name: VE-073, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) 13.2 mg were added to a four-neck flask equipped with a cooling tube, the flask was replaced with nitrogen, and the temperature was raised to the reflux temperature while stirring. The mixture was heated and stirred while maintaining the above environment for 24 hours. After the reaction was completed, the mixture was cooled to obtain a copolymer-containing solution with a solid content of about 10.7 mass%. The weight average molecular weight of the obtained liquid in GFC was about 140,000.

[0099] <Comparative Synthesis Example 7> Acid phosphooxy polypropylene glycol monomethacrylate (average number of moles of propylene oxide added: 5) (product name: PPM-5P, manufactured by Toho Chemical Industry Co., Ltd., absolute mass% (purity) 97.3 mass%) 2.30 g, methacryloylcholine chloride about 80% aqueous solution (manufactured by Tokyo Chemical Industry Co., Ltd.) 1.08 g, butyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) 1.43 g, ethanol (manufactured by Kanto Chemical Co., Ltd.) 18.2 g, pure water 12.1 g, dimethyl-1,1'-azobis (1-cyclohexane carboxylate) (product name: VE-073, manufactured by Fujifilm Wako Pure Chemical Industries Co., Ltd.) 22.8 mg were added to a four-neck flask equipped with a cooling tube, the flask was replaced with nitrogen, and the temperature was raised to the reflux temperature while stirring. The mixture was heated and stirred while maintaining the above environment for 24 hours. After the reaction was completed, the mixture was cooled to obtain a copolymer-containing solution with a solid content of about 13.4 mass%. The weight average molecular weight of the resulting liquid in GFC was about 56,000.

[0100] <Preparation Example 1> 6.60 g of pure water and 2.42 g of ethanol were added to 0.99 g of the copolymer-containing varnish obtained in Synthesis Example 1 above, and the mixture was thoroughly stirred to prepare a composition for forming a coating film. The pH was 5.8. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried in an oven at 50°C for 24 hours as a drying process. Thereafter, the wafer was thoroughly washed with a phosphate buffer solution (hereinafter abbreviated as PBS), and then dried in an oven at 50°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed by a spectroscopic ellipsometer, and was found to be 5.4 nm.

[0101] <Preparation Example 2> 6.57g of pure water and 2.44g of ethanol were added to 1.00g of the copolymer-containing varnish obtained in Synthesis Example 2 above, and the mixture was thoroughly stirred to prepare a composition for forming a coating film. The pH was 5.9. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried in an oven at 50°C for 24 hours as a drying process. After that, the wafer was thoroughly washed with PBS and then dried in an oven at 50°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed by a spectroscopic ellipsometer, and was found to be 11.1 nm.

[0102] <Preparation Example 3> 6.53 g of pure water, 2.43 g of ethanol, and 29.2 mg of 1N hydrochloric acid (Kanto Chemical Co., Ltd.) were added to 1.00 g of the copolymer-containing varnish obtained in the above Synthesis Example 3, and thoroughly stirred to prepare a composition for forming a coating film. The pH was 3.8. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried in an oven at 50°C for 24 hours as a drying process. Thereafter, the composition was thoroughly washed with PBS, and then dried in an oven at 50°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed with a spectroscopic ellipsometer, and was 16.4 nm.

[0103] <Preparation Example 4> 6.68g of pure water and 2.44g of ethanol were added to 1.02g of the copolymer-containing varnish obtained in Synthesis Example 3 above, and the mixture was thoroughly stirred to prepare a composition for forming a coating film. The pH was 5.9. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried in an oven at 50°C for 24 hours as a drying process. After that, the wafer was thoroughly washed with PBS and then dried in an oven at 50°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed by a spectroscopic ellipsometer, and was found to be 17.8 nm.

[0104] <Preparation Example 5> 2.67 g of pure water and 6.41 g of ethanol were added to 1.01 g of the copolymer-containing varnish obtained in Synthesis Example 3 above, and the mixture was thoroughly stirred to prepare a composition for forming a coating film. The pH was 6.5. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried in an oven at 50°C for 24 hours as a drying process. After that, the wafer was thoroughly washed with PBS and then dried in an oven at 50°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed by a spectroscopic ellipsometer, and was found to be 18.9 nm.

[0105] <Preparation Example 6> 2.59g of pure water, 6.38g of ethanol, and 27mg of 1N aqueous sodium hydroxide solution (Kanto Chemical Co., Ltd.) were added to 1.00g of the copolymer-containing varnish obtained in the above Synthesis Example 3, and thoroughly stirred to prepare a composition for forming a coating film. The pH was 7.4. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500rpm / 60sec, and dried in an oven at 50°C for 24 hours as a drying process. After that, it was thoroughly washed with PBS and then dried in an oven at 50°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed by a spectroscopic ellipsometer, and was 22.9nm.

[0106] <Preparation Example 7> 3.92 g of pure water and 9.59 g of ethanol were added to 1.49 g of the copolymer-containing varnish obtained in Synthesis Example 5 above, and the mixture was thoroughly stirred to prepare a composition for forming a coating film. The pH was 6.3. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried in an oven at 50°C for 24 hours as a drying process. After that, the wafer was thoroughly washed with PBS and then dried in an oven at 50°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed by a spectroscopic ellipsometer, and was found to be 5.4 nm.

[0107] <Preparation Example 8> 3.65g of pure water, 9.64g of isopropyl alcohol, and 73mg of 1N hydrochloric acid (Kanto Chemical Co., Ltd.) were added to 1.10g of the copolymer-containing varnish obtained in Synthesis Example 6 above, and thoroughly stirred to prepare a composition for forming a coating film. The pH was 3.1. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500rpm / 60sec, and dried in an oven at 50°C for 24 hours as a drying process. After that, it was thoroughly washed with PBS and then dried in an oven at 50°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed with a spectroscopic ellipsometer and found to be 6.2nm.

[0108] <Preparation Example 9> 3.70 g of pure water, 9.65 g of isopropyl alcohol, and 19 mg of 1N hydrochloric acid (Kanto Chemical Co., Ltd.) were added to 1.11 g of the copolymer-containing varnish obtained in Synthesis Example 6 above, and thoroughly stirred to prepare a composition for forming a coating film. The pH was 4.0. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried in an oven at 50°C for 24 hours as a drying process. Thereafter, the composition was thoroughly washed with PBS, and then dried in an oven at 50°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed with a spectroscopic ellipsometer, and was 4.2 nm.

[0109] <Preparation Example 10> 3.92 g of pure water and 9.59 g of ethanol were added to 1.51 g of the copolymer-containing varnish obtained in Synthesis Example 7 above, and the mixture was thoroughly stirred to prepare a composition for forming a coating film. The pH was 2.7. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried in an oven at 50°C for 24 hours as a drying process. After that, the wafer was thoroughly washed with PBS and then dried in an oven at 50°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed by a spectroscopic ellipsometer, and was found to be 4.8 nm.

[0110] <Preparation Example 11> 3.72 g of pure water, 9.59 g of ethanol, and 0.20 g of 1N sodium hydroxide aqueous solution (Kanto Chemical Co., Ltd.) were added to 1.50 g of the copolymer-containing varnish obtained in Synthesis Example 7 above, and thoroughly stirred to prepare a composition for forming a coating film. The pH was 8.0. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried in an oven at 50° C. for 24 hours as a drying process. Thereafter, the composition was thoroughly washed with PBS, and then dried in an oven at 50° C. for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed with a spectroscopic ellipsometer, and was 4.6 nm.

[0111] <Preparation Example 12> 1.50 g of the copolymer-containing varnish obtained in Synthesis Example 8 was added with 4.00 g of pure water and 9.61 g of ethanol and thoroughly stirred to prepare a composition for forming a coating film. The pH was 2.3. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried in an oven at 50°C for 24 hours as a drying process. After that, it was thoroughly washed with PBS and then dried in an oven at 50°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed with a spectroscopic ellipsometer and was 3.9 nm.

[0112] <Preparation Example 13> 3.72 g of pure water, 9.59 g of ethanol, and 0.20 g of 1N sodium hydroxide aqueous solution (Kanto Chemical Co., Ltd.) were added to 1.50 g of the copolymer-containing varnish obtained in Synthesis Example 8 above, and thoroughly stirred to prepare a composition for forming a coating film. The pH was 7.4. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried in an oven at 50°C for 24 hours as a drying process. Thereafter, the wafer was thoroughly washed with PBS, and then dried in an oven at 50°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed with a spectroscopic ellipsometer, and was found to be 3.9 nm.

[0113] <Preparation Example 14> 0.80 g of the copolymer-containing varnish obtained in Synthesis Example 9 was added with 3.54 g of pure water and 8.71 g of ethanol and thoroughly stirred to prepare a composition for forming a coating film. The pH was 3.3. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried in an oven at 50°C for 24 hours as a drying process. After that, it was thoroughly washed with PBS and then dried in an oven at 50°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed with a spectroscopic ellipsometer and was 5.1 nm.

[0114] <Preparation Example 15> 0.80 g of the copolymer-containing varnish obtained in Synthesis Example 9 was added with 3.50 g of pure water, 8.71 g of ethanol, and 45 mg of 1N aqueous sodium hydroxide solution (Kanto Chemical Co., Ltd.) and thoroughly stirred to prepare a composition for forming a coating film. The pH was 4.0. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried in an oven at 50° C. for 24 hours as a drying process. After that, it was thoroughly washed with PBS and then dried in an oven at 50° C. for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed with a spectroscopic ellipsometer and found to be 6.3 nm.

[0115] <Preparation Example 16> 0.80 g of the copolymer-containing varnish obtained in Synthesis Example 9 was added with 3.43 g of pure water, 8.71 g of ethanol, and 0.11 g of 1N aqueous sodium hydroxide solution (Kanto Chemical Co., Ltd.) and thoroughly stirred to prepare a composition for forming a coating film. The pH was 5.9. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried in an oven at 50° C. for 24 hours as a drying process. After that, it was thoroughly washed with PBS and then dried in an oven at 50° C. for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed with a spectroscopic ellipsometer and found to be 6.7 nm.

[0116] <Preparation Example 17> 3.79g of pure water, 9.45g of ethanol, and 9.6mg of 1N sodium hydroxide aqueous solution (Kanto Chemical Co., Ltd.) were added to 1.0g of the copolymer-containing varnish obtained in Synthesis Example 10 above, and thoroughly stirred to prepare a composition for forming a coating film. The pH was 4.0. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500rpm / 60sec, and dried in an oven at 50°C for 24 hours as a drying process. After that, it was thoroughly washed with PBS and then dried in an oven at 50°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed with a spectroscopic ellipsometer and found to be 6.1nm.

[0117] <Preparation Example 18> 3.77g of pure water, 9.45g of ethanol, and 35mg of 1N sodium hydroxide aqueous solution (Kanto Chemical Co., Ltd.) were added to 1.0g of the copolymer-containing varnish obtained in Synthesis Example 10 above, and thoroughly stirred to prepare a composition for forming a coating film. The pH was 6.2. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500rpm / 60sec, and dried in an oven at 50°C for 24 hours as a drying process. Thereafter, the wafer was thoroughly washed with PBS, and then dried in an oven at 50°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed with a spectroscopic ellipsometer, and was found to be 5.2nm.

[0118] <Preparation Example 19> 7.49g of ethanol and 3.61g of pure water were added to 1.00g of the copolymer-containing varnish obtained in Synthesis Example 11 above, and thoroughly stirred to prepare a composition for forming a coating film. The pH was 2.9. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried at 50°C for 3 hours as a drying process. Thereafter, the composition was thoroughly washed with a phosphate buffer solution, and then dried at 70°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed by a spectroscopic ellipsometer, and was found to be 27.7 nm.

[0119] <Preparation Example 20> 0.12 g of the copolymer obtained in Synthesis Example 12 was added with 8.33 g of ethanol and 3.61 g of pure water and thoroughly stirred to prepare a composition for forming a coating film. The pH was 2.9. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried at 50°C for 3 hours as a drying process. After that, it was thoroughly washed with a phosphate buffer solution and then dried at 70°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed by a spectroscopic ellipsometer and was 38.9 nm.

[0120] <Preparation Example 21> 7.62g of ethanol and 3.75g of pure water were added to 1.22g of the copolymer-containing varnish obtained in Synthesis Example 13 above, and thoroughly stirred to prepare a composition for forming a coating film. The pH was 2.9. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500rpm / 60sec, and dried at 50°C for 3 hours as a drying process. Thereafter, the composition was thoroughly washed with a phosphate buffer solution, and then dried at 70°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed by a spectroscopic ellipsometer, and was found to be 27.5nm.

[0121] <Preparation Example 22> 0.12 g of the copolymer obtained in Synthesis Example 14 was added with 8.33 g of ethanol and 3.59 g of pure water and thoroughly stirred to prepare a composition for forming a coating film. The pH was 2.9. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried at 50°C for 3 hours as a drying process. Thereafter, the composition was thoroughly washed with a phosphate buffer solution and then dried at 70°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed by a spectroscopic ellipsometer and found to be 39.7 nm.

[0122] <Preparation Example 23> 7.77g of ethanol and 3.86g of pure water were added to 1.31g of the copolymer-containing varnish obtained in Synthesis Example 15 above, and thoroughly stirred to prepare a composition for forming a coating film. The pH was 2.9. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried at 50°C for 3 hours as a drying process. Thereafter, the composition was thoroughly washed with a phosphate buffer solution, and then dried at 70°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed by a spectroscopic ellipsometer, and was 45.3 nm.

[0123] <Preparation Example 24> 1.31 g of the copolymer-containing varnish obtained in Synthesis Example 16 was added with 8.00 g of ethanol and 3.94 g of pure water and thoroughly stirred to prepare a composition for forming a coating film. The pH was 2.9. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried at 50°C for 3 hours as a drying process. After that, it was thoroughly washed with a phosphate buffer solution and then dried at 70°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed by a spectroscopic ellipsometer and was 27.8 nm.

[0124] <Preparation Example 25> 0.12 g of the copolymer obtained in Synthesis Example 17 was added with 8.33 g of ethanol and 3.61 g of pure water and thoroughly stirred to prepare a composition for forming a coating film. The pH was 2.9. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried at 50°C for 3 hours as a drying process. After that, it was thoroughly washed with a phosphate buffer solution and then dried at 70°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed by a spectroscopic ellipsometer and was 35.8 nm.

[0125] <Comparative Preparation Example 1> 0.80 g of the copolymer-containing varnish obtained in Comparative Synthesis Example 1 was added with 5.26 g of pure water and 1.94 g of ethanol and thoroughly stirred to prepare a composition for forming a coating film. The pH was 5.9. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried in an oven at 50°C for 24 hours as a drying process. After that, it was thoroughly washed with PBS and then dried in an oven at 50°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed with a spectroscopic ellipsometer and was 4.0 nm.

[0126] <Comparative Preparation Example 2> 0.80 g of the copolymer-containing varnish obtained in Comparative Synthesis Example 1 was added with 1.89 g of pure water, 5.11 g of ethanol, and 0.25 g of 0.1 mol / L aqueous sodium hydroxide solution (1N aqueous sodium hydroxide solution (Kanto Chemical Co., Ltd.) diluted 10 times with pure water and used) and thoroughly stirred to prepare a composition for forming a coating film. The pH was 7.5. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried in an oven at 50 ° C. for 24 hours as a drying process. Thereafter, the wafer was thoroughly washed with PBS and then dried in an oven at 50 ° C. for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed with a spectroscopic ellipsometer and found to be 3.8 nm.

[0127] <Comparative Preparation Example 3> 6.55g of pure water, 2.44g of ethanol, and 24.1mg of 1N hydrochloric acid (Kanto Chemical Co., Ltd.) were added to 1.00g of the copolymer-containing varnish obtained in Comparative Synthesis Example 3, and thoroughly stirred to prepare a composition for forming a coating film. The pH was 4.6. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500rpm / 60sec, and dried in an oven at 50°C for 24 hours as a drying process. Thereafter, the wafer was thoroughly washed with PBS, and then dried in an oven at 50°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed with a spectroscopic ellipsometer, and was 6.5nm.

[0128] <Comparative Preparation Example 4> 6.59g of pure water, 2.40g of ethanol, and 28.5mg of 1N sodium hydroxide aqueous solution (Kanto Chemical Co., Ltd.) were added to 1.00g of the copolymer-containing varnish obtained in Comparative Synthesis Example 3, and thoroughly stirred to prepare a composition for forming a coating film. The pH was 6.6. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500rpm / 60sec, and dried in an oven at 50°C for 24 hours as a drying process. Thereafter, the composition was thoroughly washed with PBS, and then dried in an oven at 50°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed by a spectroscopic ellipsometer, and was 9.1nm.

[0129] <Comparative Preparation Example 5> 3.62g of pure water, 9.66g of ethanol, and 0.16g of 1N aqueous sodium hydroxide solution (Kanto Chemical Co., Ltd.) were added to 1.5g of the copolymer-containing varnish obtained in Comparative Synthesis Example 4 above, and thoroughly stirred to prepare a composition for forming a coating film. The pH was 5.9. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried in an oven at 50°C for 24 hours as a drying process. Thereafter, the composition was thoroughly washed with PBS, and then dried in an oven at 50°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed with a spectroscopic ellipsometer, and was 5.3 nm.

[0130] <Comparative Preparation Example 6> 3.72 g of pure water, 9.66 g of ethanol, and 44 mg of 1N sodium hydroxide aqueous solution (Kanto Chemical Co., Ltd.) were added to 1.5 g of the copolymer-containing varnish obtained in Comparative Synthesis Example 5 above, and thoroughly stirred to prepare a composition for forming a coating film. The pH was 4.0. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried in an oven at 50°C for 24 hours as a drying process. Thereafter, the wafer was thoroughly washed with PBS, and then dried in an oven at 50°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed by a spectroscopic ellipsometer, and was found to be 2.6 nm.

[0131] <Comparative Preparation Example 7> 3.65g of pure water, 9.67g of ethanol, and 0.11g of 1N aqueous sodium hydroxide solution (Kanto Chemical Co., Ltd.) were added to 1.5g of the copolymer-containing varnish obtained in Comparative Synthesis Example 5 above, and thoroughly stirred to prepare a composition for forming a coating film. The pH was 5.9. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried in an oven at 50°C for 24 hours as a drying process. Thereafter, the wafer was thoroughly washed with PBS, and then dried in an oven at 50°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed by a spectroscopic ellipsometer, and was found to be 2.8 nm.

[0132] <Comparative Preparation Example 8> To 1.00 g of the copolymer-containing varnish obtained in Comparative Synthesis Example 6, 6.39 g of ethanol and 2.63 g of pure water were added and thoroughly stirred to prepare a composition for forming a coating film. The pH was 2.7. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried at 50°C for 3 hours as a drying process. Thereafter, the composition was thoroughly washed with a phosphate buffer solution and then dried at 70°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed by a spectroscopic ellipsometer and found to be 3.7 nm.

[0133] <Comparative Preparation Example 9> To 1.00 g of the copolymer-containing varnish obtained in Comparative Synthesis Example 7, 8.79 g of ethanol and 3.66 g of pure water were added and thoroughly stirred to prepare a composition for forming a coating film. The pH was 2.8. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried at 50°C for 3 hours as a drying process. Thereafter, the composition was thoroughly washed with a phosphate buffer solution and then dried at 70°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed by a spectroscopic ellipsometer and found to be 24.6 nm.

[0134] <Reference example 1> 49.75 g of ethanol was added to 0.25 g of Lipidure-CM5206 (NOF Corp.) and thoroughly stirred to prepare a composition for forming a coating film. The obtained composition for forming a coating film was spin-coated on an HMDS-treated silicon wafer at 1500 rpm / 60 sec, and dried in an oven at 50°C for 24 hours as a drying process. After that, it was thoroughly washed with PBS and then dried in an oven at 50°C for 1 hour to obtain a coating film on the HMDS-treated silicon wafer. The thickness of the coating film on the HMDS-treated silicon wafer was confirmed by a spectroscopic ellipsometer and was 25.4 nm.

[0135] <Test Example 1: Cell adhesion inhibitory effect> (Preparation of Coating Plates) The compositions for forming coating films prepared in Preparation Examples 1 to 18 and Comparative Preparation Examples 2 and 4 to 7 were added to separate wells of a 96-well cell culture plate (Corning, #351172, volume 0.37 mL, made of polystyrene) at 200 μL / well, and left to stand at room temperature for 1 hour, after which excess varnish was removed. The plate was dried at 50°C for 24 hours using an oven. Then, each coated well was washed three times with 250 μL of pure water, dried in an oven at 50°C for 1 hour, and then used for testing. As a positive control, the composition for forming coating films prepared in Reference Example 1 was used, which was coated on the wells of a 96-well cell culture plate (Corning, #351172, volume 0.37 mL, made of polystyrene) by the same method as above. As a negative control, a 96-well cell culture plate (Corning, #351172, volume 0.37 mL, made of polystyrene) without coating was used.

[0136] (Cell preparation) The cells used were mouse embryonic fibroblast C3H10T1 / 2 (DS Pharma Biomedical). The medium used for cell culture was BME medium (Thermo Fisher Scientific) containing 10% FBS (Sigma-Aldrich) and L-glutamine-penicillin-streptomycin stabilizing solution (Thermo Fisher Scientific). The cells were incubated at 37°C / CO 2 The cells were cultured for at least 2 days in a 10 cm petri dish (10 mL of medium) in an incubator with 5% carbon dioxide. The cells were then washed with 5 mL of PBS, and 1 mL of 0.25 w / v% trypsin-1 mmol / L EDTA solution (Fujifilm Wako Pure Chemical Industries, Ltd.) was added to detach the cells, which were then suspended in 10 mL of the above medium. The suspension was centrifuged (Tomy Seiko Co., Ltd., model number LC-200, 1000 rpm / 3 min, room temperature), the supernatant was removed, and the above medium was added to prepare a cell suspension.

[0137] (Cell adhesion experiment) Add 1x10 cell suspension to each well of the plate prepared above, positive control, and negative control. 4 Then, the plates were incubated at 37°C for 3 days in a 5% carbon dioxide atmosphere. 2 The mixture was placed in an incubator.

[0138] (Observation of cell attachment) After 3 days of culture, the adhesion of cells to each well of the plate prepared above, the positive control, and the negative control were compared based on observation (magnification: 4 times) using an inverted microscope (Nikon Corporation, ECLIPSE TS100-F). The results are shown in Table 1. As shown in Table 1, in the plates whose surfaces were treated with the coating film forming compositions prepared in Preparation Examples 1 to 5 and Reference Example 1 (positive control), no cell adhesion and spreading were observed, and the formation of cell aggregates (spheroids) was observed in the wells. On the other hand, in the plates whose surfaces were treated with the coating film forming compositions prepared in Comparative Preparation Examples 2 and 4 to 7 and the plate not coated (negative control), although some spheroid formation was observed, most of the cells adhered to the bottom surface of the plate and spread. As representative examples of cell observation, micrographs of the plates coated with the coating agent of Preparation Examples 3, 4, 5, Comparative Preparation Example 4, and the positive control (Reference Example 1), and each well of the negative control are shown in Figures 1 to 6.

[0139] [Table 1]

[0140] <Test Example 2: Protein adsorption suppression effect> (Creating QCM sensor (PS)) A quartz crystal oscillator (Q-Sense, QSX301) with Au vapor deposition was washed at 50 mA / 3 min using a soft etching device (Meiwafosis Co., Ltd., SEDE-GE), and immediately immersed in a solution of 0.0772 g of 2-amineethanethiol (Tokyo Chemical Industry Co., Ltd.) dissolved in 1000 mL of ethanol for 24 hours. After washing the sensor surface with ethanol, it was naturally dried, and a varnish of 1.00 g of polystyrene (PS) (Sigma-Aldrich) dissolved in 99.00 g of toluene was spin-coated on the film sensor side at 3500 rpm / 30 sec using a spin coater, and dried at 150 °C / 1 min to obtain a QCM sensor (PS).

[0141] (QCM sensor (SiO 2 ) Creation SiO 2 The deposited quartz crystal unit (Q-Sense, QSX303) was cleaned using a soft etching device (SEDE-GE, manufactured by Meiwafosis Co., Ltd.) at 50 mA for 3 min and used as it was.

[0142] (Surface-treated QCM sensor (PS) and surface-treated QCM sensor (SiO 2 Preparation of The compositions for forming coating films obtained in Preparation Examples 1 to 18, Comparative Preparation Examples 1 to 7, and Reference Example 1 were spin-coated onto QCM sensors (PS) at 3500 rpm / 30 sec, and baked in an oven at 50°C for 24 hours as a drying process. Thereafter, in a washing process, excess compositions for forming coating films were washed twice each with PBS and pure water to obtain surface-treated QCM sensors (PS) (substrates No. 1 to 26). Similarly, the compositions for forming coating films obtained in Preparation Examples 1 and 2, and Comparative Preparation Example 1 were spin-coated onto QCM sensors (SiO 2 ) and baked in an oven at 50°C for 24 hours as a drying process. After that, in the washing process, the excess coating film-forming composition was washed twice with PBS and twice with pure water, and the surface-treated QCM sensor (SiO 2) (substrates Nos. 28 to 30). As a positive control, a surface-treated QCM sensor (PS) (substrate No. 26) coated with the composition for forming a coating film obtained in Reference Example 1 was used. As a negative control, a QCM sensor (PS) (substrate No. 27) and a QCM sensor (SiO 2 ) (Substrate No. 31) was used.

[0143] (Protein adsorption experiment) The surface-treated QCM sensors (PS) (substrates No. 1 to 26) and surface-treated QCM sensors (SiO 2 ) (substrates No. 28 to 30), the negative control QCM sensor (PS) (substrate No. 27) and the QCM sensor (SiO 2 ) (Substrate No. 31) was attached to a dissipative quartz crystal microbalance QCM-D (E4, Q-Sence), and PBS was allowed to flow until a stable baseline was established with a frequency change of 1 Hz or less in 1 hour. Next, PBS was allowed to flow for approximately 10 minutes, with the stable baseline frequency set to 0 Hz. Subsequently, a 100 μg / mL PBS solution of human serum-derived γ-globulin was allowed to flow for approximately 30 minutes, and then PBS was allowed to flow again for approximately 20 minutes, after which the adsorption-induced frequency shift (Δf) of the 9th overtone was read. For analysis, the adsorption-induced frequency shift (Δf) was calculated using Q-Tools (Q-Sence) as the mass per unit area (ng / cm) described by the Sauerbrey equation. 2 ) is shown in Table 2 below as the amount of attached biological material. Substrates Nos. 1 to 18 and 28 to 29, which were coated with the coating film-forming compositions of Preparation Examples 1 to 18 according to the present invention, showed lower protein adsorption amounts than substrates Nos. 19 to 25 and 30, which were coated with the coating film-forming compositions of Comparative Preparation Examples 1 to 7, and substrates Nos. 27 and 31, which were not coated.

[0144] [Table 2]

[0145] <Test Example 3: Protein adsorption suppression effect-2> (Preparation of coating plate) The compositions for forming coating films prepared in Preparation Examples 19 to 25 and Comparative Preparation Examples 8 and 9 were added to a 96-well plate (Corning, #3363, volume 0.32 mL, made of polypropylene) at 150 μL / well per 5 wells. After standing at room temperature for 1 hour, the liquid was drained and dried in an oven at 50°C for 3 hours. Then, each well was washed three times with 200 μL of pure water and dried in an oven at 50°C for 1 hour to prepare a coated plate. As a negative control, a well of an uncoated 96-well plate (Corning, #3363, volume 0.32 mL, made of polypropylene) was used.

[0146] (Preparation of IgG-HRP Dilution Solution) Goat anti-mouse IgG antibody-HRP conjugate (Southern Biotechnology Associates) was diluted with PBS to a concentration of 1 mg / g to prepare an IgG-HRP diluted solution.

[0147] (Protein adsorption experiment) The IgG-HRP diluted solution was added to each well of the plate prepared above and to the negative control at 100 μL / well, and left to stand at room temperature for 30 minutes. The IgG-HRP diluted solution was then drained, and each well was washed three times with 200 μL of PBS. TMB solution (Sera Care, SureBlue) was added at 100 μL / well, and after 1 minute, TMB STOP solution (Sera Care) was added at 100 μL / well. The absorbance at 450 nm and 650 nm was measured using a microplate reader (TECAN, infinite M200PRO). The absorbance at 650 nm was subtracted from the absorbance at 450 nm to calculate the average absorbance of 5 wells for each coating film forming composition. The average absorbance in the negative control well was set as 100% protein adsorption, and the protein adsorption rate of the wells coated with each coating film forming composition was calculated and is shown in Table 3. It was found that the wells coated with the coating film-forming compositions of Preparation Examples 19 to 25 had a smaller amount of protein adsorption than the wells coated with Comparative Preparation Examples 8 and 9, and thus had an excellent protein adsorption inhibitory effect.

[0148] [Table 3] [Industrial Applicability]

[0149] The coating film formed from the coating film-forming composition of the present invention has an improved ability to inhibit adhesion of biological materials. Specifically, the coating film of the present invention is excellent in the ability to inhibit adhesion of biological materials such as proteins and in the ability to promote cell culture, and is therefore useful in various medical devices (e.g., medical filters, medical tubes, medical modules, artificial organs, artificial valves, surgical instruments, surgical auxiliary instruments, etc.), various research instruments (e.g., cell culture containers such as flasks, dishes, and plates, and diagnostic drug instruments for biochemical research, etc.), and various daily necessities (e.g., toiletries, personal care products, cosmetics, contact lens care products, etc.). Furthermore, the coating film-forming composition of the present invention is also useful as a blocking agent for suppressing nonspecific adsorption in enzyme-linked immunosorbent assay (ELISA) and latex agglutination methods, which are widely used in clinical diagnostic methods, and as a stabilizer for stabilizing proteins such as enzymes and antibodies.

Claims

1. The following formula (1-3): 【Chemistry 1】 (In the formula, n represents an integer of 3 to 6. A compound represented by the following formula (2): 【Chemistry 2】 (In the formula, R 3 represents a hydrogen atom or a linear or branched alkyl group having 1 to 5 carbon atoms; R 4 represents a monovalent organic group having cationic properties. and a compound represented by the following formula (3): 【Chemistry 3】 (In the formula, R 5 each independently represents a hydrogen atom or a linear or branched alkyl group having 1 to 6 carbon atoms; R 6 represents a linear or branched alkylene group having 1 to 10 carbon atoms which may be substituted with a halogen atom, and m represents an integer of 1 to 30. The present invention relates to a composition for forming a coating film having an ability to inhibit adhesion of a biological material, the composition comprising: a monomer mixture containing a compound represented by formula (3), wherein the ratio of the compound represented by formula (3) to the total mass of the monomer mixture is 2 to 40 mass %, and a solvent.

2. A coating film having an ability to inhibit adhesion of biological materials, comprising a coating film made of the coating film-forming composition according to claim 1.

3. A substrate having a surface comprising the coating film according to claim 2 and capable of inhibiting adhesion of biological materials.

4. The substrate having the ability to inhibit adhesion of a biological material according to claim 3, which is used for cell culture.

5. A method for producing a substrate having an ability to inhibit adhesion of biological materials, comprising a step of applying the coating film-forming composition according to claim 1 to a substrate, and then a step of drying the applied coating film.

6. The following formula (1-3): 【Chemistry 4】 (In the formula, n represents an integer of 3 to 6. A compound represented by the following formula (2): 【Chemistry 5】 (In the formula, R 3 represents a hydrogen atom or a linear or branched alkyl group having 1 to 6 carbon atoms; R 4 represents a monovalent organic group having cationic properties. and a compound represented by the following formula (3): 【Chemistry 6】 (In the formula, R 5 each independently represents a hydrogen atom or a linear or branched alkyl group having 1 to 6 carbon atoms; R 6 represents a linear or branched alkylene group having 1 to 10 carbon atoms which may be substituted with a halogen atom, and m represents an integer of 1 to 30. wherein the ratio of the compound represented by formula (3) to the total mass of the monomer mixture is 2 to 40 mass %.

Citation Information

Patent Citations

  • Adhesive composition

    JP1984084964A

  • Weft accumulation apparatus for loom

    JP1989085349A

  • composition

    JP1991275705A

  • Hydrous contact lens

    JP1998197831A

  • Ultraviolet curable coating agent

    JP2007231174A